Melatonin inhibits ethylene biosynthesis by regulating MdERF1/MdERF3 pathway during apple fruit ripening - Chen Li; Qian Yu; Yanmin Du; Wenhui Wang; Yajing Si; Yuling Liang; Shijiao Lin; Guangxin Yang; Weiting Liu; Aide Wang; Yinglin Ji (Postharvest Biology and Technology, 2026)

Methylome and transcriptome analysis reveal the impact of psychological stress on the skin - Bingjie Li; Ying Zou; Shenghua Tian; Laura Gonda; Andre Mahns; Tao Huang; Ludger Kolbe; Yuling Shi; Sijia Wang (Molecular Genetics and Genomics, 2026)

Quantifying the water–energy–food–carbon nexus and carbon-emission transmission pathways in grain production: Evidence from 340 Chinese cities - Yuling Wen; Zhenjie Chen; Manchun Li; Jiale Liang (Agricultural Systems, 2026)

Spatially resolved multi-omics analysis of indigenous Bacillus-fortified high-temperature Daqu - Hao Shi; Yuling Shen; Qingqing Ye; Hui Yu; Maoling Tian; Hongmei Wang; Yang Wei; Shiying Yan; Yiping Chen; Jie Zhang; Shu Li; Yang Yang; et al. (Food Research International, 2026)

Three-dimensional porous MXene-cellulose aerogel: An efficient adsorbent for sequential capture of Hg(II) and decolorization of methylene blue - Ming Li; Xiaofei Fan; Jianing Hu; Jinghong Zhang; Huining Xiao; Yuling Zhang (Desalination, 2026)

Three-dimensional thermal management: Biomass aerogel with super-hydrophilicity for high-efficiency solar evaporation via environmental energy synergy - Li Jiang; Yanyou Huang; Liangdong Ye; Yuling Lv; Ruibin Shen; Wei Wang; Yanlan Pan; Zuocai Zhang; Shaorong Lu (Desalination, 2026)

Enhanced nitrogen and phosphorus co-removal mediated by quorum sensing in novel cold-resistant strain LD-01: Mechanisms and application in hyporheic zones during freeze–thaw cycles - Dong Li; Yuling Zhang; Xiaosi Su; Tao Lang; Ruixin Wang; Yuliang Hu (Bioresource Technology, 2026)

Small-sample BOD₅ interval prediction for aeration recommendation using conformal calibrated LightTransformer-LGBM model - Wangben Zhao; Yuling Liu; Lu Wang; Shuaishuai Li; Li Sun; Shuang Ren (Journal of Environmental Chemical Engineering, 2026)

Wheat properties shape microbial succession and flavor profile in high-temperature Daqu fermentation: a multi-omics perspective - Hongmei Wang; Yuling Shen; Sican Luo; Yongxin Hu; Fuli Wen; Qian Wang; Xi Shen; Hao Shi; Yiping Chen; Xiaozhong Zhong; Songtao Wang; Yang Wei; et al. (Food Research International, 2026)

Metabolic reprogramming for post-acidification control in fermented milk via post-sterilization treatment - Han Lu; Liru Cui; Menglu Li; Yuling Xue; Yannan He; Chang Liu; Yan Wu; Shijie Wang (Food Microbiology, 2026)

Divergent temporal dynamics of yield response to nitrogen fertilization across the three major cereals - Xiaowen Zhao; Meitong Wang; Baiheng Su; Yuling Li; Xiaohe Wang; Yu Jiang; Zhenghui Liu; Ganghua Li; Yanfeng Ding; Weiwei Li (Field Crops Research, 2026)

α-Ketoglutarate attenuates ammonium chloride-induced ferroptosis by maintaining mitochondrial homeostasis in grass carp (Ctenopharyngodon idellus) hepatocytes - Yuling Zhang; Chengchen Jiang; Dapeng Li; Rong Tang (Aquatic Toxicology, 2026)

Consistent functional genes in methanogens along soil profiles in a temperate marshland - Yuling Tan; Nannan Wang; Kexin Li; Yunjiang Zuo; Jianzhao Liu; Ziyu Guo; Ming Yang; Wenwen Tan; Yuedong Guo; Yanyu Song; Fenghui Yuan; Xiaofeng Xu; et al. (Soil Ecology Letters, 2026)

Associations of pedogenic carbonate accumulation with soil organic-inorganic carbon coupling in arid croplands - Tongping Lu; Yuling Li; Xuhui Wang; Hui Guo; Bin He; Muhammad Shoaib Rana; Jie Ma; Changyan Tian; Jianfei Shi; Yugang Wang; Xiujun Wang (Agriculture, Ecosystems & Environment, 2026)

The initiation and resuspension characteristics of (micro)plastics from varied depositional environments under hydraulic disturbance - Yuling Chen; Li Lin; Xiong Pan; Yuqi Zhang (Journal of Soils and Sediments, 2026)

Mechanistic insights into the pore-scale transport and retention of microplastics: bridging physical and geochemical controls - Yaqiang Wei; Jian Liang; Yiran Chen; Jiao Zhang; Zaiyong Zhang; Ying Lyu; Zi Zhan; Yu Li; Jialun Xie; Yuling Chen; Hui Li (Water Research, 2026)

Freeze-thaw specifically regulates microbiome patterns and phosphorus acquisition strategies in the lake-groundwater interaction zone - Yuling Zhang; Ruixin Wang; Xiaosi Su; Tao Lang; Dong Li (Water Research, 2026)

Genome-wide characterization of the apple WOX family identifies MdWOX13 as a repressor of fruit ripening - Yinglin Ji; Shijiao Lin; Mingqian Wang; Yuling Liang; Meili Xin; Yanan Wang; Weiting Liu; Aide Wang; Bin Li (Postharvest Biology and Technology, 2026)

Optimized cryoablation and combinatorial chemotherapy overcome sublethal survival in pancreatic cancer cells - Yukun Cao; Xin Li; Jing Shen; Shanshan Xie; Haoyang Lin; Yuling Luo; Xinli Zhou (International Journal of Refrigeration, 2026)

Legume dominance and context-dependent benefits of cover crops for nitrogen supply in global agriculture - Xiaowen Zhao; Yuling Li; Meitong Wang; Baiheng Su; Chongxi Wen; Xiaohe Wang; Ganghua Li; Ziting Wang; Yanfeng Ding; Weiwei Li (European Journal of Agronomy, 2026)

Suitable particle-size biochar enhances resilience of potato production and soil environmental to irregular precipitation in semiarid region - Zhaoyang Li; Nan Shi; Zhimin Yang; Yubo Cao; Shimeng Fan; Musawer Abbas; Weixing Shan; Ansabayeva Assiya; Zhikuan Jia; Enke Liu; Kadambot H.M. Siddique; Ruixia Ding; et al. (Bioresource Technology, 2026)

Sustainable fabrication of hierarchical porous carbon from bagasse via recyclable template‑coupled CO2 activation and pore structure-performance correlation in phenol adsorption - Dongsheng Li; Guangwen Xu; Yuling Shan; Junwei Ding; Wenlong Yu (Bioresource Technology, 2026)

Effects of squat load and velocity on neuromuscular control strategies - Xingchen Zhang; Yao Li; Yuling Fang; Danyang Kou; Hanbing Wu; Yuan Gao; Lian Duan (European Journal of Applied Physiology, 2026)

Molecular understanding of plant pollination, fertilization, seed development and protoplast regeneration - Jiang-Guo Meng; Pu Liu; Hanxian Xiong; Wei Wang; Gang Xu; Xu Xin; Zijun Lan; Changkai Ma; Na Wang; Xuecheng Zhang; Ce Shi; Shu Chang; et al. (Science China Life Sciences, 2026)
Sexual reproduction in plants is a tightly coordinated process that underpins biodiversity, drives speciation, and serves as a foundation for modern crop improvement. Here, we synthesize recent advances in elucidating the molecular mechanisms governing major reproductive events in flowering plants, including male and female gametogenesis, pollen-pistil communication, double fertilization, embryogenesis, and endosperm-mediated seed development. We also discuss the integration of asexual propagation through protoplast regeneration, highlighting its emerging importance in plant biotechnology. Together, these insights deepen our understanding of fundamental reproductive biology and open new opportunities for the rational design of hybrid breeding systems and stress-resilient crops, with broad implications for global food security under changing climatic conditions.

Synergy of substrate, plant, and microorganism in constructed wetlands enhances chromogenic substances and nitrogen removal from real chemical tailwater - Yi Liu; Yuling Huang; Chunhua Li; Qiang He; Hong Li (Journal of Water Process Engineering, 2026)

Synthetic microbial community shields wheat from cadmium: Coordinating host metabolic reprogramming and rhizosphere microenvironment regulation - Huangxin Chen; Lin Kong; Yaoyuan Zhang; Guiyin Wang; Xin Qi; Changlian Xu; Zhanbiao Yang; Zhang Cheng; Guochun Lv; Junzhuo Cai; Lilin Wang; Yongxia Jia; et al. (Journal of Hazardous Materials, 2026)

Effects of defatting treatments on flavor components and lipid characteristics in bowl-steamed Tan lamb: A comprehensive investigation based on lipidomics and multi-platform flavor analysis - Wen Wang; Yufeng Duan; Xue Yang; Ruheng Shen; Mengying Liu; Xiaoqin Xi; Li Zhang; Long He; Yuling Qu; Liang Lin; Qiang Cheng (Food Chemistry, 2026)

Mussel-inspired engineering of green spherical cellulose adsorbents with PEI/PDA multilayers for efficient and selective mercury capture - Ming Li; Yuxin Gong; Xiaofei Fan; Jianing Hu; Shiwei Guo; Yuling Zhang; Huining Xiao (Desalination, 2026)

Antibacterial mechanisms of terpinen-4-ol against Aeromonas hydrophila - Kaiqi Lian; Xiangfeng Meng; Yuhang Wang; Shengming Ma; Xiaolong Li; Ren Ren; Yuling Liu; Lingling Zhou; Renhai Peng (Archives of Microbiology, 2026)

Natural polyphenol-mediated oxidative polymerization and degradation of emerging contaminants - Yangju Li; Hexian Qin; Jiansen Lei; Meimei Wang; Yuling Ren; Dapeng Wu; Haoran Dong (Critical Reviews in Environmental Science and Technology, 2026)

Vibration transmission characteristics of Camellia oleifera tree under excitation - Qingsong Li; Daochun Xu; Yuling Zhang; Xiaopeng Bai; Wenbin Li; Yuan He; Yuewei Ma (Computers and Electronics in Agriculture, 2026)

Early-rice straw return rnhances Cd accumulation in late-rice through increased soil Cd bioavailability and root uptake in a Cd-contaminated double-cropping rice system - Yuhui Zeng; Geyi Xu; Changsong Huang; Zhong Hu; Qian Qi; Yuling Liu; Xiao Deng; Yang Yang; Changjun Li; Si Luo (Journal of Environmental Sciences, 2026)

Assessing coastal groundwater risks from nuclear-contaminated water discharge under extreme drought and sustainable recharge solutions - Jiao Zhang; Yaqiang Wei; Yuling Chen; Zhenzhong Hu; Damià Barceló; Tian-Chyi Jim Yeh; Jiazhong Qian; Bradley A. Weymer; Zi Zhan; Xinde Cao; Hui Li (Journal of Contaminant Hydrology, 2026)

Camel milk-derived Lentilactobacillus parabuchneri L-185 produces acid-associated metabolites that inhibit MRSA growth and biofilm formation in milk - Wenjing Wang; Yuling Guo; Junkai Wang; Yaqian Liang; Meihui Tian; Yitao Li; Hui Zhang; Haihong Hao (International Journal of Food Microbiology, 2026)

Normal/inverse sandwich structure series-engineered layer-dependent double-atom catalysts featuring bridge-bonded dual‑oxygen ligands for bifunctional oxygen electrocatalysis: Machine learning-based layer-rich extended exploration and constant-potential frontier orbital analysis - Renxian Qin; Yuanrui Li; Yuling Song; Qiang Zhang; Qingjun Zhou (Chemical Engineering Journal, 2026)

Sustainable and multifunctional organohydrogel integrating high strength, environmental resilience, and humidity sensitivity for smart healthcare monitoring - Ruibing Shen; Yanyou Huang; Li Jiang; Yuling Lv; Zuocai Zhang; Liangdong Ye; Ziwei Li; Shaorong Lu (Chemical Engineering Journal, 2026)

Molecular attribute-driven hybrid SEI engineering for durable silicon anodes - Yijie Lin; Yingkang Deng; Yuling Fu; Mingjun Ma; Haolei Chen; Xinqi Chen; Shuhan Chen; Jiarong He; Lidan Xing; Weishan Li (Chemical Engineering Journal, 2026)

Enhanced puncture event detection for teleoperated needle insertion robotic system - Hongbing Li; Yubin Lan; Yuling Li; Linlong Li; Rui Wang (Medical & Biological Engineering & Computing, 2026)

How New-type Urbanization Affects Resilience of Water-energy-food System in a Rapidly Urbanizing Region? Insights from Yangtze River Delta, China - Yuling Wen; Zhenjie Chen; Manchun Li; Jiale Liang; Xiaoni Wu (Chinese Geographical Science, 2026)

Improving embryo rescue efficiency in seedless grape breeding with zeatin - Xi Chen; Shaopeng Zhao; Xinyu Chen; Mengyu Ma; Xue Wen; Yao Xiao; Yong Wang; Yuling Li; Feng Sun; Guotian Liu; Tingting Chen; Yan Xu (Protoplasma, 2026)

Antioxidant activities of three enzymatic hydrolysates from Stichopus japonicus on HaCaT cells in vitro and zebrafish in vivo - Xue Li; Fanying Meng; Tong Sun; Renfang Zhang; He Sun; Xinting Shao; You-Jin Jeon; Yong Li; Yuling Ding (Natural Product Research, 2026)

From importance to sensitivity: fuel consumption analysis of heavy-duty diesel vehicles - Yuling Song; Tianhao Liu; Tiezhu Li; Xiyuan Hu; Ruizhi Zhang; Haibo Chen (Transportation Research Part D: Transport and Environment, 2026)

Polystyrene microplastics disrupt the blood-testis barrier via CEBPB-driven lysosomal autophagy and induce ferroptosis-like injury in human sperm, compromising embryo development - Man Wu; Lei Li; Tianxin Zhao; Yuling Mao; Jiajing Lin; Xiaomin Li; Yanling Bai; Feixue Han; Shuyan Chen; Tianwen Peng; Chen Liao; Xin Ye; et al. (Journal of Hazardous Materials, 2026)

Leaching and migration behavior of EICP stabilized Zn2+ -contaminated soil under extreme acid rain conditions using range analysis: Insights from soil column experiments - Yu Song; Guohuan Chen; Chennan Huang; Xiqing Li; Junjie Zheng; Jianwei Zhang; Yuling Chen (Journal of Environmental Chemical Engineering, 2026)

Integrated approach for heavy metal ion adsorption and heterogeneous fenton denitrification using functionalized steel slag catalyst - Lingtao Liu; Yuan Xu; Zhi Gao; Jinbo Ouyang; Zhuyao Li; Yuling Zhu; Jianhua Ding; Feiqiang He (Journal of Environmental Management, 2026)

Elevated CO2 synergizes with nanoplastics to intensify arsenic mobilization, biotransformation, and plant uptake in soil-spinach systems - Wei Li; Yabo Wang; Yuling Suo; Zishu Zheng; Qiao Xu; Meiling Xu; Fen Xu; Weiqin Yin; Shengsen Wang; Xiaozhi Wang (Environmental Pollution, 2026)

Ameliorative Effects of an Antioxidant and Anti-Inflammatory Limosilactobacillus fermentum TG017 on DSS-Induced Ulcerative Colitis in Mice - Qianhao Hou; Yuling Li; Zuanyuan Huang; Honghua Hu; Xin Li; Jinyuan Zhang; Wenying Duan; Songsong Pan; Zetian Wang; Xiaodong Liu; Wei Xu; Lijun Liao (Probiotics and Antimicrobial Proteins, 2026)

Characteristics and Mechanisms of Crack Propagation in Gas-Bearing Coal Under Adsorptive Versus Non-Adsorptive Gas Conditions - Dengke Wang; Yixuan Tang; Wenrui Li; Hongtu Zhang; Biao He; Furu Kang; Shixing Fan; Baisheng Nie; Yuling Xia; Xiaofei Pang; Jinhao Yu (Natural Resources Research, 2026)

Clinical study on the interaction between iron metabolism and neuroinflammation and iron deposition in the substantia nigra of Parkinson’s disease - Yani Yao; Jiayi Li; Jiaoyang Yan; Qian Cai; Yuling Wang; Huan Xia; Tingting Feng; Peishan Li; Xinling Yang (Brain Imaging and Behavior, 2026)

Hydrocarbon subsidy-stress and divergent reduced iron–manganese thresholds shape microbial resilience in anoxic aquifers - Jili Wang; Yuling Zhang; Yang Ding; Dong Li; Yi Zhang (Water Research, 2026)

Plastic film mulch mitigates soil respiration by reducing the duration of freeze-thaw transition - Yufei Li; Kaiping Zhang; Wucheng Zhao; Yuling Li; Ningning Zhang; Pingxing Wan; Zhongke Zhou; Jianjun Yang; Hongyuan Kan; Feng Zhang (Soil and Tillage Research, 2026)

Evidence for Early Middle Jurassic wildfires: New macro-charcoal records from the Xishanyao Formation, Junggar Basin, Northern Xinjiang, China - Bing Yang; Yuling Na; Xiao Shi; Yi Wei; Xinzhi Zhang; Bing Wang; Siyuan Sun; Weitong Li (Review of Palaeobotany and Palynology, 2026)

Spatially explicit process-resolved fluxes and microbial drivers: Linking community succession to greenhouse gas emissions from full-scale industrial wastewater treatment - Weiwei Kong; Rui Dai; Zhaohui Yang; Qinyang Li; Xin Cheng; Yuling Tang; Jianfei Zhou; Bi Shi (Journal of Water Process Engineering, 2026)

l-Lysine effects on myosin carbonylation in metal-catalyzed oxidation: Implications for thermal gelation - Yuling Liu; Yuqi Wu; Ge Han; Jiaxin He; Yawen Wang; Jinfeng Pan; Shengjie Li (Food Research International, 2026)

A two-wave panel biomonitoring study of changes in urinary pesticide metabolites and their associations with liver function and inflammatory markers - Dandan Liu; Xiaotong Li; Yuling Chen; Fenfang Deng; Jia He; Chongshan Guo; Jun Yuan; Lei Tan (Environmental Research, 2026)

Stretchable multifunctional composite films with ultra-high conductivity for sustainable heating, EMI shielding, and antimicrobial applications - Yuling Lv; Yanyou Huang; Liangdong Ye; Ruibing Shen; Li Jiang; Wei Wang; Shaorong Lu (Chemical Engineering Journal, 2026)

Characteristics and source apportionment of atmospheric fine particulate-bound mercury (PBM2.5) in abandoned mercury mining areas in southwestern China - Yuling Kuang; Longchao Liang; Shasha Liu; Xian Dong; Fang Zhu; Xiaohang Xu; Zhuo Chen; Yayun Li; Yaji Li; Guangle Qiu (Acta Geochimica, 2026)

Advances on Sporisorium reilianum: microbiology along with chemistry, bioactivity, and application - Yihua Wang; Yansong Meng; Zezhuang Hao; Haohan Yang; Zhixin Shen; Denghui Yu; Ye Wang; Shuguang Guan; Yuling Ding; Yong Li (Folia Microbiologica, 2026)

Proteomic characterization of feather decorations and extinct buffalo glue during early Iron Age China - Binjie Qi; Zhiguo Zhang; Jiajun Wang; Zhipeng Li; Yuling He; Shishan Niu; Xiaomeng Li; Huiyun Rao; Yimin Yang (Science Bulletin, 2026)

Oligo-cyanobacterial microalgae-bacteria granular sludge for mitigating cyanotoxin risk: Cultivation, characteristics, and formation mechanism - Bingdang Wu; Yu Zhai; Shiqi Li; Yuling Yang; Donglin Cao; Wanjun Wu; JingJing Yang; Tianyin Huang; Jinlong Zhuang (Journal of Environmental Management, 2026)

Responses of viral communities and viral-encoded auxiliary metabolic genes to long-term fertilization practices under different land-use types - Xunqi Chen; Dong Zhu; Yuling Zheng; Xiaomin Li; Guoxin Sun; Xiaoming Li; Longjun Ding (Journal of Environmental Sciences, 2026)

Nanomaterials in the food industry: applications and potential health risks - Wenrui Li; Suyu Lin; Luyao Zhang; Jiachen Yu; Yuling Cai; Di Wu; Yongning Wu; Guoliang Li (Food Chemistry, 2026)

Deep fertilization effects on potato production and GHG emissions depend on soil C:N:P-enzyme interactions: Evidence from a 4-year study - Zhaoyang Li; Nan Shi; Yixuan Yuan; Haiyang Chang; Yuling Meng; Weixing Shan; Moskvicheva Elena; Ansabayeva Assiya; Zhikuan Jia; Xiaolong Ren; Kadambot H.M. Siddique; Ruixia Ding; et al. (European Journal of Agronomy, 2026)

Cellulose-based ultralight foam with dual-scale porosity from hybrid fibers for sustainable oil-water separation - Weiqiang Li; Jingge Liu; Meiying Li; Haitao Lin; Jian Fang; Xiaoqiao Wang; Jianchu Xu; Yuling Li; Junze Zhang; Xinheng Li; Gang Li (Carbohydrate Polymers, 2026)

Development of a high ethyl hexanoate-producing strain via ARTP mutagenesis and fermentation optimization using agricultural by-products - Yuling Li; Zhiqiang Wang; Renzhi Wan; Xin Zeng; Bingyue Xin; Biao Zhang; Jie Qiao; Deyin Zhao; Mingtao Zhao; Youyu Xie; Zhuangzhuang Jiang; Huawei Zeng; et al. (Biocatalysis and Agricultural Biotechnology, 2026)

Tryptophan metabolism alterations in neurological and psychiatric diseases: Molecular mechanisms and pharmacological targets - Yuanyuan Wang; Yuling Chen; Hongtao Li; Jingjing Sang; Chen Chen; Lei Xu; Weiting Zhang; Baichen Xiong; Ruijia Jiang; Xinyu Ren; Yao Chen; Haopeng Sun; et al. (Metabolic Brain Disease, 2026)

A decision support system for coagulant dosage using explainable NSGA-II optimized stacking framework - Wangben Zhao; Yuling Liu; Lu Wang; Shuaishuai Li; Li Sun; Ren Shuang (Journal of Water Process Engineering, 2026)

Corrigendum to “Soil iGDGTs temperature dependence: From the Tibetan Plateau to the global scale and its implications for the Holocene temperature conundrum” [Geochim. Cosmochim. Acta 411 (2025) 233–249] - Yanwu Duan; Shuo Hao; Qing Sun; Josef P. Werne; Aifeng Zhou; Yuling Zhou; Yuanxin Li; Mengjing Li; Lin Chen; Xianyong Cao; Fahu Chen (Geochimica et Cosmochimica Acta, 2026)

Integrated metabolomics to systematically monitor quality indicators and metabolic dynamics in stored Ophiocordyceps sinensis - Chuyu Tang; Yuejun Fan; Bing Jia; Haoxu Tang; Yuling Li; Xiuzhang Li (Food Chemistry, 2026)

Adjusting fertilization depth for sustainable potato production in arid and semi-arid regions - Zhaoyang Li; Yukang Wang; Nan Shi; Yixuan Yuan; Lianjun Wei; Weixing Shan; Medelbek Meruyert; Ansabayeva Assiya; Zhikuan Jia; Kadambot H.M. Siddique; Ruixia Ding; Peng Wu; et al. (Field Crops Research, 2026)

Multistimuli-responsive degradable metal-organic framework nanoplatform potentiates photoimmunotherapy for hepatocellular carcinoma via cGAS-STING pathway activation - Yahui Wu; Zhipu Liu; Yi Zhang; Senfeng Zhao; Miaoqing Li; Ruiyang Zhang; Jiahui Cao; Peng Liu; Liming Song; Yin Liu; Yunpeng Zhai; Weijie Wang; et al. (Chemical Engineering Journal, 2026)

Deciphering the mechanism of aristolochic acid I-driven hepatocellular carcinoma through integrated network toxicology and bioinformatics - Yuling Liang; Xing Ning; Qiuxia Chen; Shuqiao Zhang; Huishan Luo; He Yu; Tangjiaqi Li; Baoguo Sun; Shijun Zhang (Naunyn-Schmiedeberg's Archives of Pharmacology, 2026)

Epicoccum sorghinum as a leaf spot disease-causing pathogen in Lithocarpus litseifolius in China - Yuling Wang; Meng Li; Changjiang Liu; Guolin Cai; Mengxing Wang; Wuping Yan; Jianfeng Chen (Crop Protection, 2026)

Effects of stocking density on growth and glucose metabolism in rainbow trout (Oncorhynchus mykiss) - Zhao Li; Zhuohang Feng; Shuangyue Luo; Yaxin Wang; Yuling Xu; Kang Dong; Zhishuai Hou; Qinfeng Gao; Shuanglin Dong (Aquaculture, 2026)

Biomass organohydrogel toward green wearable sensors: Enhancing high and low temperature sensing properties, UV shielding properties, and long-term cycling durability - Ruibing Shen; Qiaoyan Wei; Liangdong Ye; Liling Zhang; Yanyou Huang; Yuling Lv; Ziwei Li; Zuocai Zhang; Xiaokun Han; Shaorong Lu (Chemical Engineering Journal, 2026)

Molecular Dissection of Response Mechanism and Leaf Color Variation in Ulmus Pumila Cv.‘Jinye’ Under Saline-Alkali Stress - Shufang Yan; Yichao Liu; Shuxiang Feng; Gongdan Zhou; Yuling Li; Yinran Huang (Journal of Crop Health, 2026)

A novel antiviral peptide Laby A1/A3 precursor-SUMO against PCV2 replication with broad-spectrum antiviral potential - Yan Zhang; Yuling Li; Qiqi Xia; Jingyuan Zhang; Yanmin Li; Long Zhou; Zijing Guo; Zhidong Zhang (Veterinary Microbiology, 2026)

Interpretable machine learning model based on floc images for monitoring the coagulation process - Shuaishuai Li; Yuling Liu; Zhixiao Wang; Peng Guo; Chuanchuan Dou; Wangben Zhao (Process Safety and Environmental Protection, 2026)

Development and simulation-based optimization of a Split-flow low-aerobic/anoxic/Oxic process integrating partial nitrification -denitrification with step feeding for enhanced nitrogen removal - Li Sun; Yuling Liu; Hao Shu; Yaohui Shao; Zhiqiang Xu; Jiayu Qi (Journal of Water Process Engineering, 2026)

Supramolecular calix[6]arene-COF with pocket-like cavities for host-guest recognition-based SERS detection of tryptamine and seafood freshness monitoring - Jiana Lin; Ying Chen; Gongke Li; Yuling Hu (Food Chemistry, 2026)

An epoxy-based composite coating with CoFeNi/N-doped carbon for integrated flame retardancy, photothermal conversion, and microwave absorption in thermal management - Biyu Huang; Yuling Wang; Yusheng Tong; Jie Shen; Haopeng Zhang; Lei Liu; Meng Liu; Shaoxiang Li; Chuanmei Jiao; Xilei Chen (Chemical Engineering Journal, 2026)

Causal links between pandemics and weather and air pollution in 39 cities, 2020–2021 - Ting Shi; Bo Zhou; Ailin Qi; Kai Wang; Yunpeng Ao; Chenyi Li; Yuling Zhang (Atmospheric Pollution Research, 2026)

Mechanistic insights into isopropyl myristate-stimulated monascus pigment biosynthesis via untargeted metabolomics - Renzhi Wan; Zhiqiang Wang; Yuling Li; Xin Zeng; Bingyue Xin; Jie Qiao; Huawei Zeng; Liang Zhang (World Journal of Microbiology and Biotechnology, 2026)

The Role of HIF-1α/BNIP3 Pathway in Hippocampal Neuronal Autophagy in Epilepsy - Huimin Kuang; Youshi Meng; Xinran Qin; Kai Qian; Chi Gong; Sijun Li; Lin Zhang; Xiaohang Gan; Yuling Lu; Yuan Wu (Molecular Neurobiology, 2026)

Anticancer Activity of Endophytic Bacterial Extracts from Potentilla supina in HepG2 and HCT116 Cells - Xia Li; Xinxin Zhao; Jinqiu Gui; Yuling Liu; Guiru Kong (Current Microbiology, 2026)

SFG enhances apoptosis of hepatocellular carcinoma by inhibiting tunneling nanotubes-mediated mitochondrial transport in the tumor microenvironment - Shasha Kong; Yuling Liu; Ruying Tang; Hui Li; Hongmei Lin; Longfei Lin (Apoptosis, 2026)

Bio-inspired fabrication of heterostructured porous core-shell PANI@Cu2O/CMC composite beads for green catalysis in A3 and decarboxylative A3 couplings - Shuyao Zhang; Ting Lin; Yuling Huang; Jiayi Huang; Meiling Xue; Zhihao Shan; Yiqun Li (Sustainable Chemistry and Pharmacy, 2025)

Utilizing phosphogypsum-derived CaAl LDH-chitosan to remove Pb2+ from oil/gas field wastewater: Adsorption behavior and competitive mechanism - Jing Bai; Qijia You; Yushuan Peng; Zhihao Li; Yuling Zhang; Qiulin Deng; Huiwei Liao; Faqin Dong; Xiaofeng Zeng; Zixun Yan (Process Safety and Environmental Protection, 2025)

Antimicrobial mechanism of moderate-temperature-assisted high-voltage pulsed electric field combined with vanillin against Saccharomyces cerevisiae and its application in red raspberry juice - Yuling He; Bin Li; Xiyun Sun; Xu Xie; Junwei Huo; Fuzhi Xuan; BaoRu Yang; Ying Zhou; Yuehua Wang (Innovative Food Science & Emerging Technologies, 2025)

Soil iGDGTs temperature dependence: From the Tibetan Plateau to the global scale and its implications for the Holocene temperature conundrum - Yanwu Duan; Shuo Hao; Qing Sun; Josef P. Werne; Aifeng Zhou; Yuling Zhou; Yuanxin Li; Mengjing Li; Lin Chen; Xianyong Cao; Fahu Chen (Geochimica et Cosmochimica Acta, 2025)

Recombinant PD1 liposome loading nintedanib for pulmonary fibrosis therapy in mice - Qian Luo; Ying Xie; Jiarui Xu; Yuxin Ren; Shuyuan Xiong; Hongrui Zhang; Yuling Chen; Haocheng Chen; Jinling Wang; Pengyu Huang; Liyu Sun; Peishan Li; et al. (Chemical Engineering Journal, 2025)

Divergent environmental controls on branched tetraethers along precipitation gradients in soils of the Tibetan Plateau - Yanwu Duan; Yuling Zhou; Shuo Hao; Qing Sun; Josef P. Werne; Aifeng Zhou; Lin Chen; Yuanxin Li; Mengjing Li; Xianyong Cao; Fahu Chen (Chemical Geology, 2025)

Anthropogenic aerosol feedbacks intensify air pollution and weather variability over China - Jixiang Li; Haipeng Yu; Andrea Pozzer; Kai Tang; Chenhui Jia; Zeyong Hu; Siyu Chen; Yunsai Zhu; Yuling Hu; Bofei Zhang; Hongyu Luo; Zekui Jiang; et al. (Atmospheric Environment, 2025)

Genome-wide identification and functional analysis of the polyamine metabolism-related genes in Foxtail millet (Setaria Italica L.) - Liuan Hao; Tao Wang; Yangyang Wei; Pengtao Li; Yuling Liu; Quanwei Lu; Huawen Zou; Renhai Peng (Functional & Integrative Genomics, 2025)

Genome-wide identification and analysis of paclobutrazol-resistance gene family in cotton and the positive role of GhPRE3 in salt stress and drought stress resistance - Shuaikang Geng; Jingjing Zhai; Bingkai Cui; Huiyun Shan; Zili Liu; Jiahui Li; Cong Wang; Yuling Liu; Pengtao Li; Quanwei Lu; Zihan Xiao; Xiaoping Pan; et al. (Functional & Integrative Genomics, 2025)
Compared with other transcription factors, much less studies have been performed on paclobutrazol-resistance (PRE), a subgroup of the extensive bHLH transcription factor gene family, and the research in cotton was also limited. By utilizing the PRE genes and their conserved domains identified in Arabidopsis, a total of 23, 22, 11, and 12 PRE genes were identified from two major cultivated cotton species and their two ancestors, respectively. The cotton PRE gene family was categorized into three subgroups based on evolutionary tree analysis. Motif and intron analyses indicated that the PRE gene has remained highly conserved throughout evolution. Collinearity analysis indicated that gene duplication, particularly through fragment replication, has significantly contributed to the expansion of the cotton PRE family. An exploration of the conserved elements within the PRE gene family uncovered numerous elements associated with plant stress resistance. Additionally, cotton transcriptome and qRT-PCR analysis showed that PRE genes were associated with a variety of abiotic stresses, including salt, drought, and cold treatments. Subcellular localization experiments indicated that the GhPRE3 gene is associated with membrane proteins. Finally, we selected the GhPRE3 gene for a VIGS experiment, which revealed that under salt stress and drought stress conditions, the wilting of leaves in the GhPRE3- silenced plants was significantly more severe than that observed in the control group, with T-AOC levels notably lower and MDA levels significantly higher. Overexpression of GhPRE3 enhanced seed germination and root development in transgenic Arabidopsis thaliana under salt stress and drought stresses. This suggests that GhPRE3 plays a positive regulatory role in cotton tolerance to salt and drought stressed, providing a reference for molecular genetic breeding of cotton with salt and drought tolerance.

Genome-wide identification and functional analysis of TCX gene family and the critical role of GhTCX17 in response to drought and salt stress in cotton - Yangyang Wei; Jingjing Zhai; Shuaikang Geng; Shaoliang Zhang; Yongqing Zhao; Bingkai Cui; Huiyun Shan; Yanhua Li; Cong Wang; Pengtao Li; Yuling Liu; Quanwei Lu; et al. (Functional & Integrative Genomics, 2025)

Identification of the STY13 gene family across the entire genome and an analysis of the essential function of GhSTY13-12 in cotton’s response to abiotic stress - Shaoliang Zhang; Huiyun Shan; Xiaopei Bo; Jiahui Li; Zili Liu; Pengtao Li; Yuling Liu; Xiaojie Yang; Quanwei Lu; Sumei Wan; Renhai Peng; Yangyang Wei; et al. (Functional & Integrative Genomics, 2025)

Vagus nerve stimulation: innovative applications in the field of hand function rehabilitation - Yize Chen; Yuling Gao; Jiaqi Zhou; Shengchao Zhang; Tong Li; Zhenni Zhang; Xiaoyang Gong; Yong Liu (Cognitive Neurodynamics, 2025)

A sequential HT-Bayesian method offers deep insights for precise groundwater contaminant characterization - Hui Li; Zi Zhan; Yuling Chen; Tian-chyi Jim Yeh; Yiran Chen; Jiao Zhang; Yaqiang Wei (Water Research, 2025)

High-throughput discrimination of chlorogenic acid isomers in Lonicerae Japonicae Flos by U-shaped mobility analyzer-mass spectrometer - Meng Ding; Luwei Zheng; Ao Zhou; Yuling Li; Yiming Wang; Xiaoqiang Zhang; Wenjian Sun; Wen Gao; Ping Li; Hua Yang (Food Chemistry, 2025)

Analysis of metabolic characteristics of highly resistant grass carp bred on the basis of constitutive expression level of innate immune molecules - Yuling Wei; Bin Li; Zhe Long; Zongjun Du; Zhao Lv; Tiaoyi Xiao (Fish & Shellfish Immunology, 2025)

Long-term plastic film mulching increased maize yield and water use efficiency - Linrong Han; Yuling Li; Jun Zhu; Zhongke Zhou; Wucheng Zhao; Yifan Yang; Wenjuan Zhang; Xuetong Zhang; Feng Zhang (Field Crops Research, 2025)

Silica aerogel composites with excellent thermal insulation for building applications - Song He; Hongcheng Li; Yuling Zhang; Hongliang Sheng; Yajun Huang (Energy and Buildings, 2025)

Confinement-effect adsorbents based on titanium-based lithium ion sieve for efficient lithium adsorption under natural pH conditions - Yuling Ma; Yu Han; Yan Yang; Tao Zhang; Jinxin Yao; Yuchen Li; Yongchen Zong; Wei Wang (Chemical Engineering Journal, 2025)

Cascade nanozyme of multi-antioxidant Mn-doped carbon dots counters cytokine storm in acute lung injury - Pengli Gao; Hongchengcheng Chen; Yuling Bai; Jiaqian Li; Xiaoli Wang; Jingying Jiang (Chemical Engineering Journal, 2025)

Rapid detection of bloodstream infection bacteria directly from positive blood cultures by ultraviolet photoionization time-of-flight mass spectrometry - Zhuoya Li; Quanfeng Liao; Yi Xie; Yuling Xiao; Xiaoli Zou; Wenwen Li (Analytica Chimica Acta, 2025)

Study on the spatio-temporal variation and trade-off/synergy relationship of ecosystem service value in Western Hubei based on dynamic equivalent method - Weiying Cheng; Yuan Li; Yuling Peng (Environment, Development and Sustainability, 2025)

Genome-Wide Identification of the DVR Gene Family and Expression Analysis of GDF8 Genes in Qihe Gibel Carp - Jinyan Shan; Yuling Liu; Kaiqi Lian; Xianghui Xiao; Jun Ma; Ren Ren; Xiaolong Li; Guoqiang Wei; Youyi Kuang; Renhai Peng (Fishes, 2025)
(1) Background: The BMP/GDF (Bone Morphogenetic Protein/Growth Differentiation Factor) subfamily (Decapentaplegic-Vg1-related, DVR) within the transforming growth factor beta (TGF-β) superfamily plays critical roles in governing biological developmental processes and physiological functions. (2) Methods: In this study, we systematically investigated the DVR gene family in hexaploid Qihe gibel carp (Carassius gibelio var. Qihe) through comprehensive genomic identification, phylogenetic analysis, chromosome mapping, and cis-regulatory element prediction. The experimental design for gene expression analysis involved collecting samples from multiple tissues (brain, muscle, liver, kidney, etc.) and different developmental stages (20, 45, and 60 days post hatching, dph) to examine the expression patterns of four GDF8 genes using quantitative real-time PCR (qRT-PCR). (3) Results: We identified 50 DVR members in Qihe gibel carp. Phylogenetic analysis classified the 50 DVR family members into 20 distinct protein types, with 29 BMPs (Bone Morphogenetic Proteins) and 21 GDFs (Growth Differentiation Factors) identified. All 50 DVR proteins of Qihe gibel carp have similar TGF-β domains except for four BMP1 proteins. Chromosomal localization revealed widespread distribution of DVR members across 36 chromosomes, a pattern potentially linked to the hexaploid genome of Qihe gibel carp. Genes within the same subgroup exhibited conserved intron–exon architectures and similar intron numbers; syntenic conservation within subgroups may reflect functional constraints after polyploidization, implying evolutionary pressure to maintain functional domains. Through spatiotemporal expression profiling, we uncovered functional divergence among four GDF8 (myostatin) paralogs: GDF8-1 and GDF8-2 were predominantly expressed in brain and muscle tissues (dorsal and caudal), while GDF8-3 and GDF8-4 showed hepatic, cerebral, and renal specificity. Intriguingly, all paralogs exhibited a gradual upregulation during late development (20–60 days post hatching, dph), with peak expression staggered between 45 dph (GDF8-1/2) and 60 dph (GDF8-3/4). (4) Conclusions: These findings suggest that GDF8 plays a critical regulatory role in the growth and development of Qihe gibel carp. Collectively, these results provide a foundation for further investigations into the functional roles of the DVR gene family during the ontogenetic development of this species.

Cuproptosis is involved in small intestinal toxicity in the paraffins during pregnancy - Juan Tang; Zemin Xu; Mengna Jiang; Chao Luo; Xiaoyan Li; Yuling Jiang; Yi Qu; Jialing Ruan; Xiaoke Wang; Meihua Zheng; Wing-Cheung Law; Xinyuan Zhao (Toxicology Letters, 2025)

Microplastics and gynecological tumors: An emerging environmental health concern - Yuling HU; Zhihui SONG; Jingwen LI; Feiyi YANG; Ling LI (Reproductive Toxicology, 2025)

Preparation of Co-Ce modified sludge-based catalyst and its application in CO2 photothermal catalytic reduction - Shu Hao; Luo Xinzeng; Liu Yuling; Jia Yang; Dou Chuanchuan; Li Bo (Fuel, 2025)

Dam operation changed the transport patterns of microplastics - from a global perspective - Yuling Chen; Li Lin; Yi Li; Yu Gao; Lei Dong; Xiong Pan; Ziwei Guo (Environmental Pollution, 2025)

Botany, chemistry, bio-activity, and application of Polygonatum odoratum (Mill.) Druce: a comprehensive review - Yiwen Zhang; Xueyan Li; Denghui Yu; Zhaoyi Yang; Zhixin Shen; Yansong Meng; Yuling Ding; Yong Li (Naunyn-Schmiedeberg's Archives of Pharmacology, 2025)

Huang Lian Jie Du Decoction Prevents Chronic Alcoholic Encephalopathy and Improves Gut Microbiota Imbalance in Mice - Yun Chen; Lianyan Jiang; Yuan Zhang; Yuling Shen; Mao Li; Dongdong Yang; Bo Wang (Molecular Neurobiology, 2025)

Deletion of ZNRF2 Exacerbates MPTP-Induced Parkinson’s Disease by Activating mTOR-Mediated Neuroinflammatory Pathways - Fanshi Zhang; Jingqing Xu; Qi Yuan; Yuling Xie; Li Zhang; Jun Zhang; Zucai Xu; Mei Liu (Molecular Neurobiology, 2025)

Tissue-specific effects of stocking density on fatty acid composition and liver metabolism in rainbow trout (Oncorhynchus mykiss) - Zhao Li; Kang Dong; Yuling Xu; Yaxin Wang; Zhishuai Hou; Qinfeng Gao; Shuanglin Dong (Fish Physiology and Biochemistry, 2025)

Untargeted lipidomic deep-profiling of human plasma via high-performance aza-Prilezhaev aziridination-LC-MS: Unraveling C C isomeric signatures of Charcot-Marie-Tooth disease - Yuling Li; Weiran Zhao; Xiang Xiang; Yunlei Hu; Xiaoqiang Zhang; Wenjian Sun; Xiaoxuan Liu (Analytica Chimica Acta, 2025)

Regulation of coagulant dosage in water treatment based on explainable integrated time-series deep learning models - Wangben Zhao; Yuling Liu; Ren Shuang; Wang Lu; Shuaishuai Li; Chenxu Zhao; Chuanchuan Dou; Hao Shu (Process Safety and Environmental Protection, 2025)

Exothermicity analyses and energy efficiency of a novel liquid cooling strategy in suppressing thermal runaway propagation of a lithium-ion battery module - Hanyu Zhao; Xuguang Tang; Lun Li; Junhui Gong; Yuling Xiao (Process Safety and Environmental Protection, 2025)

Influence of supports in CuFe-based catalysts for hydrogenation of CO2 to ethanol - Yangqin Liu; Yuling Ma; Xin Pu; Xin Han; Lei Ye; Lingtao Kong; Jiangbing Li; Jian Zhang; Haitao Xu; Xinglong Qin; Jichang Liu (Fuel, 2025)

A copper-doped mesoporous nanoplatform with dual enzyme-mimic activities for amplified cuproptosis and immune response - Qingqing Xu; Shuaipeng Feng; Yue Cao; Yang Li; Zhu Liu; Qiuling Deng; Jiaru Lan; Donghua Di; Yuling Mao; Siling Wang; Qinfu Zhao (Chemical Engineering Journal, 2025)

Plant-insect interaction from the Middle Jurassic Haifanggou Formaton in Huludao, western Liaoning and its geological implications - Yuling Na; Tao Li; Yunfeng Li; Chunlin Sun; Xiao Shi; Xuemei Li (Palaeobiodiversity and Palaeoenvironments, 2025)

TAT-T407 Mitigates Apoptosis and Cognitive Impairments Following Cerebral Ischemia Through Disruption of TRPV1-CDK5 Interaction - Qian Feng; Ying Li; Xiangru Wen; Hui Li; Chengyu Qi; Nan Wang; Guang Zhu; Yanyan Fu; Changdong Liu; Dan Liu; Zhen Zhang; Fan Yang; et al. (Molecular Neurobiology, 2025)

Molecular Characterization and Antiviral Function Against GCRV of Complement Factor D in Barbel Chub (Squaliobarbus curriculus) - Yu Xiao; Zhao Lv; Yuling Wei; Mengyuan Zhang; Hong Yang; Chao Huang; Tiaoyi Xiao; Yilin Li (Fishes, 2025)
The barbel chub (Squaliobarbus curriculus) exhibits remarkable resistance to grass carp reovirus (GCRV), a devastating pathogen in aquaculture. To reveal the molecular basis of this resistance, we investigated complement factor D (DF)—a rate-limiting serine protease governing alternative complement pathway activation. Molecular cloning revealed that the barbel chub DF (ScDF) gene encodes a 1251-bp cDNA sequence translating into a 250-amino acid protein. Crucially, bioinformatic characterization identified a unique N-glycosylation site at Asn139 in ScDF, representing a structural divergence absent in grass carp (Ctenopharyngodon idella) DF (CiDF). While retaining a conserved Tryp_SPc domain harboring the catalytic triad (His61, Asp109, and Ser204) and substrate-binding residues (Asp198, Ser219, and Gly221), sequence and phylogenetic analyses confirmed ScDF’s evolutionary conservation, displaying 94.4% amino acid identity with CiDF and clustering within the Cyprinidae. Expression profiling revealed constitutive ScDF dominance in the liver, and secondary prominence was observed in the heart. Upon GCRV challenge in S. curriculus kidney (SCK) cells, ScDF transcription surged to a 438-fold increase versus uninfected controls at 6 h post-infection (hpi; p

Seasonal freeze-thaw significantly alters the distinct aquifers solute transport, microbial community assembly patterns, and molecular ecological networks in the hyporheic zone - Dong Li; Yuling Zhang; Xiaosi Su; Jili Wang; Ningfei Li (Water Research, 2025)

Impact of electric vehicle downsizing on shared mobility considering externalities - Li Li; Yuling Shi; Dianchao Lin; Yongliang Lu (Transportation Research Part D: Transport and Environment, 2025)

Novel EDTA modified steel slag-based catalyst for NO removal through heterogeneous Fenton processes - Lingtao Liu; Yuan Xu; Zihua Hu; Jianying Yang; Zhuyao Li; Yuling Zhu; Jianhua Ding; Jiawei Li; Feiqiang He (Journal of Hazardous Materials, 2025)

Nanocellulose improves viscoelasticity and freeze-thaw stability of water-in-oil emulsion gels - Xin Hong; Mingjun Shu; Yuling Zhou; Jieying Li; Jinwei Li (Food Chemistry, 2025)

Ginger exosome-covered mesoporous polydopamine nanoplatform ameliorates liver fibrosis via antioxidation and macrophage phenotypic transformation - Junhong Zhou; Hongwei Xu; Zhu Liu; Yuling Mao; Yian Li; Liwan He; Shuaipeng Feng; Donghua Di; Siling Wang; Qinfu Zhao (Chemical Engineering Journal, 2025)

Construction of yeast two-hybrid cDNA library and identification of interacting protein with McHDRa/b in Matricaria chamomilla L. - Honggang Wang; Luyao Yu; Shuangshuang Li; Jin Wang; Wenjing Cheng; Siqing Zhu; Feng Shi; Yuling Tai; Yi Yuan (Plant Molecular Biology, 2025)

Characteristic analysis of floc size distribution and image texture evolution in chemical coagulation process - Shuaishuai Li; Yuling Liu; Zhixiao Wang; Chuanchuan Dou; Wangben Zhao; Hao Shu (Process Safety and Environmental Protection, 2025)

Root hair: An important guest-meeting avenue for rhizobia in legume–Rhizobium symbiosis - Jingwen Xiao; Wenxu Liu; Bicong Wu; Yuling Zhang; Sha Li; En Li (Plant Science, 2025)

Characteristics of lipid accumulation induced by high-altitude environment improve the total antioxidant capacity of Ophiocordyceps sinensis - Tao Wang; Chuyu Tang; Mengjun Xiao; Min He; Yuling Li; Xiuzhang Li (Food Chemistry, 2025)

Encapsulation of cinnamaldehyde with protein-based nanoemulsions for strawberry preservation: Influence of protein types - Jiayan Lu; Yunyan Hua; Mengjia Guo; Laixue Ni; Yuling Cai; Yungang Cao; Longfeng Wang; Weiwei Li (Food Packaging and Shelf Life, 2025)

Effects of temperature and salinity on CO2 fluxes dynamics and respiration metabolism in the sea cucumber Apostichopus japonicus (Selenka) - Yaoping Mei; Yuling Xu; Qinfeng Gao; Zhao Li; Shuanglin Dong (Marine Pollution Bulletin, 2025)

Understanding citrus aroma: Changes induced by postharvest treatments of fresh fruit - Shuxun Liu; Yuling Cai; Ying Lou; Yan Zhao; Mingfeng Cao; Ping Li; Qing Gu (Postharvest Biology and Technology, 2025)

Environmental impacts and carbon reduction benefits of mining photovoltaic systems: A case study of Ningdong coal base - Yongliang Zhang; Peixian Li; Ximin Cui; Guorui Wang; Yuling Zhao; Guangyao Zhu (Journal of Cleaner Production, 2025)

Exogenous melatonin enhancing the accumulation of flavonoids and carotenoids in wolfberry fruit at cold storage - Rong Jiang; Zhiqiang Wang; Yixin Jia; A. Biao; Yuan Zong; Chao Yang; Minglin Li; Hongjiao Wang; Yuling Zhao; Ying Wang; Shaohua Zeng (Food Research International, 2025)

Evaluation of the freshness (TVB-N) of pork patty during storage based on PLS-DA, SVM and BP-ANN models - Hui Lu; Aiying Song; Ming Li; Xianqi Yao; Yuling Cai; Longlong Dong; Dacheng Kang; Yunguo Liu (Food Control, 2025)

Cellulosic aerogel-encapsulated carbon dots for enhanced mercury detection and adsorption in aqueous systems with subsequent upcycling for organic pollutant photocatalytic degradation - Ming Li; Panpan Zhang; Jianwei Mao; Jianfeng Li; Dongqing Wang; Bo Xu; Jin Zhou; Jinghong Zhang; Qianyong Cao; Yuling Zhang; Huining Xiao (Desalination, 2025)

A self-reinforcing, self-healing, and shape memory polybutadiene-based polyurethane via disulfide bonds for healable flexible sensors - Haolei Shi; Yu Shi; Liping Ren; Wei Zhang; Yuan Ji; Jichi Zhang; Xu Zhong; Yuling Liang; Jidong Dong; Yadong Wu; Wei Li; Dawei Zhang; et al. (Chemical Engineering Journal, 2025)

Correction to: Failure mechanism and stability evaluation of rockslides with oblique intersecting faults as well as mitigation measures for slope − top platform collapse - Huaixin Li; Changgen Yan; Yuling Shi; Hengxing Lan; Han Bao; Weifeng Sun; Zhe He; Dingle Ma; Kui Wen; Jiamin Hu (Landslides, 2025)

Conjugated Iminodibenzyl Dyes Incorporating Phenolic Hydroxyl Group and Strong Electron Donating or Accepting Groups for Facilitating ESIPT and Proton Transfer in Six- or Seven-Membered Cycles - Xiaozhuan Qin; Hongru Li; Yufei Wang; Yuling Li; Xiaochuan Li (Journal of Fluorescence, 2025)

Isotopic and hydrochemical evidence for the origins of unconventional gases in the Middle and Lower Jurassic coal measures in the Fukang area of Junggar Basin, NW China - Jie Xiang; Jiandong Li; Xianqing Li; Xiaomin Ma; Jie Sun; Zhuo Zou; Yuling Qin (International Journal of Coal Geology, 2025)

Transcriptomics and metabolomics provide the difference of unique odor between natural and cultivated Ophiocordyceps sinensis and the biosynthetic pathway of key volatile compounds - Tao Wang; Mengjun Xiao; Chuyu Tang; Jianzhao Qi; Yuling Li; Xiuzhang Li (Food Bioscience, 2025)

Development of a model for maize stalk lodging resistance based on plant bending strength and trait selection - Guanmin Huang; Yuling Guo; Weiming Tan; Mingcai Zhang; Zhaohu Li; Yuyi Zhou; Liusheng Duan (Field Crops Research, 2025)

Hierarchical MXene@PBA@IL nanohybrids towards high-efficiently enhance fire safety of epoxy resin - Jirui Qu; Gaoyuan Li; Biyu Huang; Haopeng Zhang; Yuling Wang; Richeng Lian; Lei Liu; Lei Yang; Baojun Li; Xilei Chen; Chuanmei Jiao (Chemical Engineering Journal, 2025)

Comparative transcriptomics of susceptible and resistant Cucumis metuliferus upon Meloidogyne incognita infection - Xiaoxiao Xie; Junru Lu; Runmao Lin; Jian Ling; Zhenchuan Mao; Jianlong Zhao; Qihong Yang; Shijie Zheng; Yan Li; Richard G. F. Visser; Yuling Bai; Bingyan Xie (Planta, 2025)

Comparative transcriptomic analysis of heterotic maize development during kernel filling - Wenyu Li; Xiangkun Guo; Wen Yao; Keke Li; Qi Zheng; Yongbiao Yu; Zhiwei Zhang; Yan Wang; Weigang Yao; Ju Wu; Huan Hu; Lingwei Hu; et al. (Plant Molecular Biology, 2025)

Peptides from Dalian Stichopus japonicus: Antioxidant Activity and Melanogenesis Inhibition In Vitro Cell Models and In Vivo Zebrafish Models Guided by Molecular Docking Screening - Xue Li; Fanying Meng; Tong Sun; Zezhuang Hao; Yihua Wang; Yunfei Jiang; Ye Wang; Yong Li; Yuling Ding (Marine Biotechnology, 2025)

Failure mechanism and stability evaluation of rockslides with oblique intersecting faults as well as mitigation measures for slope − top platform collapse - Huaixin Li; Changgen Yan; Yuling Shi; Hengxing Lan; Han Bao; Weifeng Sun; Zhe He; Dingle Ma; Kui Wen; Jiamin Hu (Landslides, 2025)

Evaluation of Heavy Metals and Essential Minerals in the Hair of Children with Autism Spectrum Disorder and Their Association with Symptom Severity - Xulan Zhou; Xiaochun Xia; Liming Li; Yaohui Ye; Qihui Chen; Mingyue Ke; Qian Cui; Yuling He; Yiting Chen; Shaoqing Lin; Wenlong Liu; Juan Wang (Biological Trace Element Research, 2025)

N-doped carbon nanotubes encapsulated Ni3ZnC0.7 nanoparticles catalyst for peroxymonosulfate activation: Heterojunction structure and N-doping enhance electron transfer capability - Qihao Sun; Huiyuan Deng; Na Zhao; Junjie You; Zhicheng Pan; Bo Xing; Yuling Ye; Bo Lai; Xinye Yang; Xinjie Wang; Yunhui Lu; Jian Li; et al. (Chemosphere, 2025)

Strychni Semen and two alkaloidal components cause apoptosis in HK-2 cells through TRADD-MAPK/NF-κB pathway - Wenyi Tian; Yuling Li; Fengzhi Liu; Hui Liu; Chen Li; Lin Bao; Xiaodong Liang (Toxicon, 2025)

An AP2/ERF transcription factor GhERF109 negatively regulates plant growth and development in cotton - Huiyun Shi; Ghulam Qanmber; Zuoren Yang; Yuling Guo; Shuya Ma; Sheng Shu; Yujun Li; Zhongxu Lin; Fuguang Li; Zhao Liu (Plant Science, 2025)

Influences of natural organic acids on the degradation of atrazine in water by pyrite-mediated Fenton oxidation - Yuling Zheng; Fang Li; Chen Yan; Wei Yang; Jia Wen; Biao Song (Journal of Water Process Engineering, 2025)

Interface performance and damage strength model of guar gum−treated fiber−reinforcement loess slope protection material - Huaixin Li; Changgen Yan; Jing Ren; Yuling Shi; Han Bao; Zhuolong Jia; Zherui Liang (Journal of Cleaner Production, 2025)

Evolutionary trends and photothermal catalytic reduction performance of carbon dioxide by MOF-derived MnOx - Dou Chuanchuan; Liu Yuling; Shu Hao; Li Shuaishuai; Shi Qiyuan; Luo Xinzeng (Fuel, 2025)

Encapsulation of oleanolic acid into cyclodextrin metal-organic frameworks by co-crystallization: Preparation, structure characterization and its effect on a zebrafish larva NAFLD model - Meng Li; Dongxia Hu; Dian Zhang; Guangya Xu; Di Wu; Chengcheng Gao; Linghan Meng; Xiao Feng; Weiwei Cheng; Zhenjiong Wang; Yuling Yang; Xiaozhi Tang (Food Research International, 2025)

Exploration on antifreeze potential of thawed drip enzymatic hydrolysates on myofibrillar proteins in pork patties during freeze-thaw cycles - Xiaoyu Han; Yang Li; Ying Wang; Jinpeng Wang; Wendi Teng; Longlong Dong; Yuling Cai; Jinxuan Cao; Yuemei Zhang (Food Chemistry, 2025)

China's non-energy-intensive sectors have greater carbon reduction potential: Based on a three-tier SDA approach from energy substitution perspective - Chang Qin; Feng Dong; Yangfan Li; Xiaoyun Zhang; Yuling Pan; Caixia Li; Jue Cui (Environmental Impact Assessment Review, 2025)

Endogenous stem cell repair strategy via electromechanical interaction for stress injury - Honglin Xiang; Fan Wang; Qing Zhang; Zeyu Han; Yefei Lei; Neng Lai; Ke Jiang; Hanfeng Yang; Wenguo Cui; Yuling Li (Chemical Engineering Journal, 2025)

Technological progress accelerates CO2 emissions peaking in a megacity: Evidence from Shanghai, China - Wei Li; Zhenjie Chen; Manchun Li; Yuling Wen (Sustainable Cities and Society, 2025)

Host-guest mediated recognition and rapid extraction of Fusarium mycotoxins in cereals by nickel ferrite magnetic calix[4]arene-derived covalent organic framework fabricated in room-temperature - Jiana Lin; Gongke Li; Yuling Hu; Qisheng Zhong (Food Chemistry, 2025)

Fabrication and characterization of lysozyme fibrils/Zein complexes for resveratrol encapsulation: Improving stability, antioxidant and antibacterial activities - Min Huang; Yuling Song; Han Wang; Hao Li; Rongmi Zhou; Qing Cao; Lijuan Dong; Gerui Ren; Di Wu; Qunfang Lei; Wenjun Fang; Dan Deng; et al. (Food Chemistry, 2025)

Natural selection of Lacticaseibacillus paracasei mutant: Weaken the post-acidification of fermented milk - Lei Li; Han Lu; Yuling Xue; Yannan He; Baohua Zhao; Lianzhong Ai; Shijie Wang (Food Bioscience, 2025)

Constructing a low-cost total Ce(III)-based adsorbent for efficient removal and recovery of phosphate - Tao Zhang; Junle Li; Dongqing Liu; Yuling Ma; Yu Han; Sujie Shan; Kai Sun; Elena V. Zelinskaya; Aijie Wang; Hongliang Sun; Wei Wang (Chemical Engineering Journal, 2025)

Biochar supporting and sulfidation synergistically affect reactivity of nanoscale zerovalent iron towards sulfamethoxazole - Mi Li; Tiao Zhang; Jing Wang; Xiaoyu Xiao; Xinyi Zeng; Cui Hu; Xiaoming Zou; Wei Hui; Yuling Zheng (Chemical Engineering Journal, 2025)

Effective enhancement of ramie anaerobic continuous flow degumming by chitosan and its microbiological mechanism - Xuehui Xie; Yiting Qin; Haonan Mo; Zhuoyu Zhao; Yuling Li; Yanxue Ma; Yao Sun; Dongyang Li; Ziyi Wu; Na Liu; Qingyun Zhang; Xiaoguang Chen (Bioresource Technology, 2025)

The genus Quercus: metabolites, biological activity and mechanisms of action - Lulu Jiang; Shuanghui Yin; Guangyue Wang; Xinting Shao; Ye Wang; Yong Li; Yuling Ding (Phytochemistry Reviews, 2025)

Nuclear factor NF-YA4a regulates salt stress tolerance and juvenile-adult phase transition in Pyrus - Yingjie Yang; Yuling Mei; Xueping Li; Ran Wang; Chunhui Ma; Jiankun Song; Zhenhua Cui; Jianlong Liu; Xiaozhi Zhou; Dingli Li (Horticulture, Environment, and Biotechnology, 2025)

Revealing the molecular links between coronary heart disease and cognitive impairment: the role of aging-related genes and therapeutic potential of stellate ganglion block - Zhehao Jin; Yuling Xing; Pengyu Duan; Yonghong Bi; Xiaoyan Li; Weiyu Feng; Bing Zhang (Biogerontology, 2025)

Impact of white matter hyperintensity location on outcome in acute ischemic stroke patients: a lesion-symptom mapping study - Yuling Peng; Dan Luo; Peng Zeng; Bang Zeng; Yayun Xiang; Dan Wang; Ying Chai; Yongmei Li; Xiaoya Chen; Tianyou Luo (Brain Imaging and Behavior, 2025)

Functional analysis of (E)-β-farnesene synthases involved in accumulation of (E)-β-farnesene in German chamomile (Matricaria chamomilla L.) - Yuling Tai; Haiyan Wu; Lu Yang; Yi Yuan; Youhui Chen; Honggang Wang; Yifan Jin; Luyao Yu; Shuangshuang Li; Feng Shi (Plant Science, 2025)

Effect of mainstream-forced-entrainment control strategy on the combustion performance of a cavity-based combustor - Yuling Zhao; Mingyu Li; Cheng Gong (Fuel, 2025)

Visible light-powered photodynamic antibacterial chlorophyllin-derived metallochlorins - Yuling Xue; Kuoran Xing; Max Jing Rui Tham; Bang Lin Li; Narattam Sikdar; Lai Peng Leong; Ching Hua Lee; Justin Jang Hann Chu; Wee Han Ang; David Tai Leong (Chemical Engineering Journal, 2025)

Collagen IV/laminin-1 coated temozolomide-prodrug hydrogel for recruiting and eradicating residual glioma cells - Yufu Zhu; Jiaqi Jin; Yang Lu; Diancheng Hang; Xuefeng Zhang; Gang Zhao; Qing Wang; Yuling Li; Hongmei Liu (Chemical Engineering Journal, 2025)

Quantitative study on the relationship between land use and land cover and diatom community in urban streams - Xiang Chen; Weiqi Zhou; Wenjuan Yu; Mingwei Yang; Dong Sheng; Kangyong Li; Na Li; Yuling Ou; Feng Wei (Environmental Science and Pollution Research, 2024)

Temperature sensitivity of soil respiration to elevated temperature and nitrogen availability - Yufei Li; Kaiping Zhang; Yuling Li; Pingxing Wan; Zhongke Zhou; Wucheng Zhao; Ningning Zhang; Ning Chai; Zhixin Li; Yalan Huang; Feng Zhang (Soil and Tillage Research, 2024)

A novel approach to estimate land surface temperature from landsat top-of-atmosphere reflective and emissive data using transfer-learning neural network - Shuo Xu; Dongdong Wang; Shunlin Liang; Aolin Jia; Ruohan Li; Zhihao Wang; Yuling Liu (Science of The Total Environment, 2024)

Constructing a visual detection method for coagulation effect based on image feature machine learning - Shuaishuai Li; Yuling Liu; Zhixiao Wang; Chuanchuan Dou; Wangben Zhao; Hao Shu (Journal of Water Process Engineering, 2024)

Multi-omics analyses of the mechanism for formation of key aroma-active compounds in blood orange wine fermented by Pichia kudriavzevii - Shuxun Liu; Ying Lou; Yan Zhao; Yuling Cai; Mingfeng Cao; Yixian Li; Ping Li; Qing Gu (Food Research International, 2024)

Lactobacillus plantarum LP104 improved intestinal and brain inflammation by modulating TLR4 pathway and gut flora in alcohol liver injury mice - Yue Zhang; Yuxuan Ma; Yuling Fan; Yuexin Gao; Yamei He; Yu Wang; Bo Nan; Jingsheng Liu; Xia Li; Yuhua Wang (Food Bioscience, 2024)

Study on the physical properties of red clay cured by different external admixtures combined with enzyme induced carbonate precipitation technology - Yu Song; Yuling Chen; Jichun Cheng; Wei Liu; Jiaqi Li; Jianwei Zhang; Junjie Zheng (Carbonates and Evaporites, 2024)

Colorectal Cancer Complicated with Chronic Schistosoma Japonicum Infected: A Case Report - Shan Li; Yuling Shen; Ting Li; Yanqing Shi (Acta Parasitologica, 2024)

Determining optimal nitrogen concentration intervals throughout lettuce growth using fluorescence parameters - Peizhe Li; Zhangtong Sun; Yongxia Yang; Miao Lu; Huimin Li; Haoran Yan; Jin Hu; Yuling Song (Computers and Electronics in Agriculture, 2024)

A multi-perspective assessment of satellite surface Ozone products in China: Spatiotemporal variability, land cover impacts and pollution monitoring capability - Jian Wang; Yuling Du; Tianxiang Cui; Jibo Yue; Lin Sun; Haiping Si; Ping Dong; Hebing Liu; Yong Li; Lei Shi (Remote Sensing Applications: Society and Environment, 2024)

Comparative analysis of anaerobic degumming effects on different bast fibers from the angle of enzyme activity and microbial community structure - Yiting Qin; Xuehui Xie; Haonan Mo; Yuling Li; Xiaoguang Chen; Yanxue Ma; Zhuoyu Zhao; Hangmi Zheng; Yao Sun; Dongyang Li; Ziyi Wu; Na Liu; et al. (Journal of Cleaner Production, 2024)

Constructing a visual detection model for floc settling velocity using machine learning - Shuaishuai Li; Yuling Liu; Zhixiao Wang; Chuanchuan Dou; Wangben Zhao (Journal of Environmental Management, 2024)

Population pharmacokinetics of fluconazole for prevention or treatment of invasive candidiasis in Chinese young infants - Honghong Wang; Dandan Li; Yongjiang Jiang; Jing Liang; Qiaoai Yu; Linghong Kuang; Yuling Huang; Dongjie Qin; Ping Li; Jing He; Feng Xu; Xueli Li; et al. (Naunyn-Schmiedeberg's Archives of Pharmacology, 2024)

Vadose-zone characteristic pollutants distribution, microbial community structure and functionality changes in response to long-term leachate pollution of an informal landfill site - Dong Li; Yuling Zhang; Furong Yu; Jili Wang; Xinying Zhang; Liuyuan Feng; Tao Lang; Fengtian Yang (Science of The Total Environment, 2024)

The shifting pattern of CO2 source sink in a subtropical urbanizing lightly eutrophic lake - Rongjie Yang; Huixing Song; Qiao Qin; Yingying Chen; Di Li; Yuling Qiu; Kezhu Lu; Yike Tan; Qingqing Chen; Xinhao Cao; Shiliang Liu (Science of The Total Environment, 2024)

A transition from arbuscular to ectomycorrhizal forests halts soil carbon sequestration during subtropical forest rewilding - Ruiqiang Liu; Xuhui Zhou; Yanghui He; Zhenggang Du; Hongyang Chen; Yuling Fu; Liqi Guo; Guiyao Zhou; Lingyan Zhou; Jie Li; Hua Chai; Changjiang Huang; et al. (Science of The Total Environment, 2024)

Changes in compound temperature and precipitation extremes from combined effects of multiple circulation factors over China - Jingpeng Zhang; Tianbao Zhao; Juanjuan Zhang; Yuling Ren; Zhi Li (Journal of Hydrology, 2024)

The impact of population change on social-ecological systems’ vulnerability: A case of the Qinling-Daba Mountains of Southern Shaanxi in China - Runyang Li; Jia Chen; Xinjun Yang; Sha Yin; Ruohan Shi; Yuling Bai; Li Xu (Journal of Cleaner Production, 2024)

Preparation, bioactivities, and food industry applications of tuber and tuberous roots peptides: A review - Mengjia Zhu; Fei Li; Yuling Zhang; Jia Yu; Yuxi Wei; Xiang Gao (Food Chemistry, 2024)

Effects of OSA-starch-fatty acid interactions on the structural, digestibility and release characteristics of high amylose corn starch - Mingyue Liu; Xiaoyan Wang; Yihui Li; Danni Jin; Yuling Jiang; Yong Fang; Qinlu Lin; Yongbo Ding (Food Chemistry, 2024)

A new intracellularly regulated release pattern controlled by coordinated carrier cracking and drug release - Xinyue Zhang; Ye He; Zhiqi Wang; Ying Zhang; Wen Guo; Shuai Li; Xinyu Wang; Yuling Mao; Siling Wang (Chemical Engineering Journal, 2024)

A review of the research progress on Artemisia argyi Folium: botany, phytochemistry, pharmacological activities, and clinical application - Hailong Wang; Yiwen Zhang; Denghui Yu; Yong Li; Yuling Ding; Yuan He; Li Sun (Naunyn-Schmiedeberg's Archives of Pharmacology, 2024)

Aging properties of polyethylene and polylactic acid microplastics and their adsorption behavior of Cd(II) and Cr(VI) in aquatic environments - Xinying Zhang; Yuling Zhang; Dong Li; Jili Wang; Yang Ding; Yiliang Wang; Liuyuan Feng; Yuliang Hu (Chemosphere, 2024)

Protective effects of the secondary metabolites from Quercus salicina Blume against gentamicin-induced nephrotoxicity in zebrafish (Danio rerio) model - Shuang-Hui Yin; Wen-Jun Zhang; Lu-Lu Jiang; Guang-Yue Wang; You-Jin Jeon; Yuling Ding; Yong Li (Comparative Biochemistry and Physiology Part C: Toxicology & Pharmacology, 2024)

Carboxymethylcellulose and rare earth metal cation self-assembly: Tunable encapsulation of carbon dots in a multifunctional transparent film - Zhihao Shan; Jiayi Huang; Yuling Huang; Yuping Zhou; Yiqun Li (Chemical Engineering Journal, 2024)

Study on the chemical composition and anti-fungi activities of anthraquinones and its glycosides from Rumex japonicus Houtt. - He Sun; Dandan Xiao; Xue Li; Tong Sun; Fanying Meng; Xinting Shao; Yuling Ding; Yong Li (Journal of Natural Medicines, 2024)

Epidemiologic trends and changes in humoral immunity and lymphocyte subsets levels among hospitalized children with Mycoplasma pneumoniae infection during 2019–2023 - Linyan Tang; Kaiwen Zheng; Lanlan Ma; Ling Chen; Yuling Zhao; Li Li; Ke Wang; Jing Zhang; Xing Chen (European Journal of Clinical Microbiology & Infectious Diseases, 2024)

Aggregation-induced electrochemiluminescence based on intramolecular charge transfer and twisted molecular conformation for label-free Immunoassay - Jinxia Liu; Wenjun Ming; Jing Zhang; Xiaobo Zhou; Yuling Qin; Li Wu (Analytica Chimica Acta, 2024)

Monitoring nonlinear large gradient subsidence in mining areas through SBAS-InSAR with PUNet and Weibull model fusion - Yuanjian Wang; Ximin Cui; Chunqing Ge; Yuhang Che; Yuling Zhao; Peixian Li; Yue Jiang; Xiaoqing Han (Environmental Science and Pollution Research, 2024)

Effects of ocean acidification and nitrogen limitation on the growth and photophysiological performances of marine macroalgae Gracilariopsis lemaneiformis - Yuling Yang; Wei Li; Yahe Li; Nianjun Xu (Frontiers in Marine Science, 2024)
To investigate the effects of ocean acidification (OA) and nitrogen limitation on macroalgae growth and photophysiological responses, Gracilariopsis lemaneiformis was cultured under two main conditions: ambient (Low CO 2 , LC, 390 μatm) and CO 2 enriched (High CO 2 , HC, 1000 μatm), with low (LN, 7 μmol L -1 ) and high (HN, 56 μmol L -1 ) nitrate. High CO 2 levels decreased growth under both LN and HN treatments. HC reduced Chl a , carotenoids, phycoerythrin (PE), and phycocyanin (PC) under HN conditions, while only Chl a decreased under LN conditions. NO 3 - uptake rate was restricted under LN compared to HN, while HC enhanced it under HN. Net photosynthetic O 2 evolution rates did not differ between CO 2 and nitrate treatments. Dark respiration rates were higher under HN, further boosted by HC. The stimulated effective quantum yield (Y(II)) corresponded to decreased non-photochemical quenching (NPQ) under HN conditions. Nitrate, not CO 2 , showed significant effects on the relative electron transport rate (rETR max ), light use efficiency (α) and saturation light intensity (I k ) that with lowered rETR max and α under LN culture. Our results indicate that OA may negatively affect Gracilariopsis lemaneiformis growth and alter its photophysiological performance under different nutrient conditions.

Intelligent Detection of 3D Anchor Position Based on Monte Carlo Algorithm - Zekai Cui; Xueli Zhang; Yuling Chen; Liang Cao; Zeguo Zhang; Zuchao Liang; Meijie Zhou; Jiawen Li; Xiaowen Li (Journal of Marine Science and Engineering, 2024)
With the increase in port throughput and the development of the trend of large-scale ships, selecting applicable anchor positions for ships and ensuring the rational and comprehensive utilization of anchorage areas have become a key issue in utilizing the rate of anchorage resources, ensuring the safety of ships anchoring operations and promoting the development of the shipping industry. Existing anchor position selection and detection algorithm studies are limited to a two-dimensional plane for ship anchor position selection, with few studies considering intelligent detection algorithms for safe ship anchoring water depths based on three-dimensional space, considering conditions such as wind and waves. By considering water depth conditions and the objectives of anchorage safety issues, this study proposes an intelligent detection method for ship anchor detection to find the ship’s ideal anchor location in the anchorages by applying the Monte Carlo algorithm. In the processing step, in combination with the Monte Carlo random plane anchor position detection algorithm and Monte Carlo random sampling water depth detection method, the anchor position circle radius model, safe spacing model, anchoring area detection model and safe water depth model are used for examining the anchorage area for awaiting the ship in three-dimensions. To verify the accuracy of the proposed model, based on the scale of common ship types and considering the most conservative parameters, a series of simulation experiments are conducted to check whether the water depth meets the requirements and fully ensure the safety of the experimental results. The research results indicate that the detection almost cover the whole anchorage area and obtain safe water depth restrictions. This method helps to improve the efficiency of ship anchoring and makes actual anchoring operations safer. Under the premise of ensuring sufficient safe spacing between ships, the anchorage ground can accommodate more ships and simulate multi-type ship anchor position detection operations concerning various ship-type parameters to further ensure the safety of ship anchoring.

Design, construction and application of algae-bacteria synergistic system for treating wastewater - Weihao Li; Lijun Wang; Xi Qiang; Yuling Song; Wenhui Gu; Zengling Ma; Guangce Wang (Journal of Environmental Management, 2024)

Rapid construction of double macrocycles, hierarchical covalent organic framework with size-sieving and host-guest recognition for selective adsorption and targeted analysis of mycotoxins in cereals - Zenghui Xie; Jiana Lin; Yuling Hu; Gongke Li; Qisheng Zhong (Chemical Engineering Journal, 2024)

EVA1A reverses lenvatinib resistance in hepatocellular carcinoma through regulating PI3K/AKT/p53 signaling axis - Xiaokun Liu; Xiao Gao; Yuling Yang; Di Yang; Qingming Guo; Lianhui Li; Shunlong Liu; Wanxin Cong; Sen Lu; Lin Hou; Bin Wang; Ning Li (Apoptosis, 2024)

Heavy metals in a typical industrial area-groundwater system: Spatial distribution, microbial response and ecological risk - Dong Li; Yang Ding; Yi Zhang; Xinying zhang; Liuyuan Feng; Yuling Zhang (Chemosphere, 2024)

Distribution, mobilization, risk assessment and source identification of heavy metals and nutrients in surface sediments of three urban-rural rivers after long-term water pollution treatment - Xu Yao; Zheng Wang; Dandan Li; Hejia Sun; Chong Ren; Yilei Yu; Feifei Pei; Yuling Li (Science of The Total Environment, 2024)

An aeration requirements calculating method based on BOD5 soft measurement model using deep learning and improved coati optimization algorithm - Wangben Zhao; Yuling Liu; Xing Zhou; Shuaishuai Li; Chenxu Zhao; Chuanchuan Dou; Hao Shu (Journal of Water Process Engineering, 2024)

Bi-directional association between outdoor or social activities and cognitive function: do the PM2.5 exposure catalyze the detrimental inactivity-poor cognition cycle? - Yuling Jiang; Yifei Wu; Yang Hu; Shaojie Li; Longbin Ren; Jingjing Wang; Mingzhi Yu; Rui Yang; Zhouwei Liu; Nan Zhang; Kejia Hu; Yunquan Zhang; et al. (Environmental Research, 2024)

South and Southeast Asia controls black carbon characteristics of Meili Snow Mountains in southeast Tibetan Plateau - Pengfei Chen; Shichang Kang; Yuling Hu; Tao Pu; Yajun Liu; Shijin Wang; Mukesh Rai; Ke Wang; Lekhendra Tripathee; Chaoliu Li (Science of The Total Environment, 2024)

Quantitative in situ Raman spectroscopy investigation on HSO4− dissociation at high pressures (up to 420 MPa) and its geological implication - Hao Cui; Zimeng Li; Richen Zhong; Joël Brugger; Yuling Xie; Chang Yu; Huan Chen; Yifan Ling (Geochimica et Cosmochimica Acta, 2024)

Heterogeneous variations in wintertime PM2.5 sources, compositions and exposure risks at urban/suburban rural/remote rural areas in the post COVID-19/Clean-Heating period - Zhiyong Li; Zhuangzhuang Ren; Chen Liu; Zhi Ning; Jixiang Liu; Jinming Liu; Zhen Zhai; Xiaohua Ma; Lan Chen; Yuling Zhang; Longkai Bai; Shaofei Kong (Atmospheric Environment, 2024)

Expert Consensus on Big Data Collection of Skin and Appendage Disease Phenotypes in Chinese - Shuang Zhao; Zhongling Luo; Ying Wang; Xinghua Gao; Juan Tao; Yong Cui; Aijun Chen; Daxing Cai; Yan Ding; Heng Gu; Jianying Gu; Chao Ji; et al. (Phenomics, 2024)

The effects of canopy gaps on soil nutrient properties: a meta-analysis - Mengting Hou; Guangqi Zhang; Yuling Li; Jiaqi Xie; Lipeng Zang; Qingfu Liu; Danmei Chen; Mingzhen Sui; Yuejun He (European Journal of Forest Research, 2024)

Evaluation of Opaque-2 effects on popping characteristics using iTRAQ-based proteome profiles in popcorn - Yongbin Dong; Qi Zheng; Junjie Zhu; Qingling Shi; Siqi Jiang; Mengying Pan; Xinyue Zhang; Long Zhang; Yuling Li (Euphytica, 2024)

Antibiotic resistance, biofilm formation, and molecular epidemiology of Staphylococcus aureus in a tertiary hospital in Xiangyang, China - Yitong Tang; Na Xiao; JiuMing Zou; Yuling Mei; Yue Yuan; Menghuan Wang; Zezhou Wang; Yunjuan Zhou; Yiyuan Chen; Shichao Li (Brazilian Journal of Microbiology, 2024)

Mycorrhizal associations relate to stable convergence in plant–microbial competition for nitrogen absorption under high nitrogen conditions - Zhenggang Du; Lingyan Zhou; Madhav P. Thakur; Guiyao Zhou; Yuling Fu; Nan Li; Ruiqiang Liu; Yanghui He; Hongyang Chen; Jie Li; Huimin Zhou; Ming Li; et al. (Global Change Biology, 2024)
Nitrogen (N) immobilization (Nim, including microbial N assimilation) and plant N uptake (PNU) are the two most important pathways of N retention in soils. The ratio of Nim to PNU (hereafter Nim:PNU ratio) generally reflects the degree of N limitation for plant growth in terrestrial ecosystems. However, the key factors driving the pattern of Nim:PNU ratio across global ecosystems remain unclear. Here, using a global data set of 1018 observations from 184 studies, we examined the relative importance of mycorrhizal associations, climate, plant, and soil properties on the Nim:PNU ratio across terrestrial ecosystems. Our results show that mycorrhizal fungi type (arbuscular mycorrhizal (AM) or ectomycorrhizal (EM) fungi) in combination with soil inorganic N mainly explain the global variation in the Nim:PNU ratio in terrestrial ecosystems. In AM fungi‐associated ecosystems, the relationship between Nim and PNU displays a weaker negative correlation ( r = −.06, p r = .25, p

Construction of cellulose-based hybrid hydrogel beads containing carbon dots and their high performance in the adsorption and detection of mercury ions in water - Ming Li; Panpan Zhang; Jianwei Mao; Jianfeng Li; Yuling Zhang; Bo Xu; Jin Zhou; Qianyong Cao; Huining Xiao (Journal of Environmental Management, 2024)

Enhanced cadmium absorption and tolerance of rice epiphytic microbes by iron oxide nanoparticles - Siduo Ding; Zhong Hu; Yuling Liu; Li Li; Yuhui Zeng; Doudou Jin; Anwei Chen; Jihai Shao; Pin Su; Si Luo (International Biodeterioration & Biodegradation, 2024)

Research progress of microfluidics-based food safety detection - Wenjun Jiang; Qu Tang; Yidan Zhu; Xijuan Gu; Li Wu; Yuling Qin (Food Chemistry, 2024)

Neutral pH photoenzymatic activity of Au-doped g-C3N4 nanosheet for colorimetric detection of total antioxidant capacity in food samples - Xianming Li; Wentong Fan; Honghu Tang; Dongdong Li; Yuling Xiao; Bin Yang; Yi Zhao; Peng Wu (Food Chemistry, 2024)

Recent advances and prospects of persistent luminescent materials in public health applications - Yuechen Li; Conglin Guo; Jige Yuan; Xiaoxiao Yang; Haiwei Ji; Mingmin Wu; Li Wu; Yuling Qin (Chemical Engineering Journal, 2024)

Evolved Late Mesozoic continental arc: Constraints of detrital zircons from the western East China Sea - Yuling Deng; Changhai Xu; Shunli Gao; Qiang Fu; Yuanyuan Li (International Geology Review, 2024)

The ameliorative effect of probiotics on diet-induced lipid metabolism disorders: A review - Yu Wang; Zhiyi Ai; Xinyue Xing; Yuling Fan; Yue Zhang; Bo Nan; Xia Li; Yuhua Wang; Jingsheng Liu (Critical Reviews in Food Science and Nutrition, 2024)

Effects of transition-metal ions on the reduction of N-nitrosodimethylamine in water by zinc - Ying Han; Xiaoping Zheng; Beibei Jiang; Yuling Tang; Hongyuan Liu; Kemin Zhang; Yaping Guo; Jun Li (Journal of Environmental Chemical Engineering, 2024)

Lithologic control of priming effect in subtropical forest - Tiangang Tang; Qi Zhang; Ruitong Fu; Pengpeng Duan; Yuling Zhang; Xinyi Yang; Kelin Wang; Dejun Li (CATENA, 2024)

Experimental study of building natural ventilation with pendulum velocity anemometer - Yuling Lv; Min Wang; Wentao Wu; Wenzhe Shang; Huimin Yao; Jianwei Li; Gerald DS. Quoie Jr; Hong Zhang; Xiong Shen (Building and Environment, 2024)

Effects of Dietary Zinc on Growth Performance, Digestive Enzyme Activities, Antioxidant Status, and Immune Responses of Sea Cucumber Apostichopus japonicus - Yuling Xu; Qinfeng Gao; Shuanglin Dong; Zhishuai Hou; Yaoping Mei; Xueqi Li; Kang Dong; Zhao Li (Biological Trace Element Research, 2024)

Near-full-length genome analysis of two novel HIV second recombinant forms in Hebei, China - Yuxin Feng; Jianhua Lu; Lijing Wang; Yuling Wang; Jingyun Li; Hanping Li; Lin Li; Erhei Dai (Archives of Virology, 2024)

The photo- and microbial degradation kinetics and pathways of sulfadoxine in seawater elucidated by liquid chromatography coupled with time-of-flight mass spectrometry - Guowen Tang; Yuling Chen; Shanshan Lin; Xiaolin Li (Chemosphere, 2024)

Mortality risk of people living with HIV under hypothetical intervention scenarios of PM2.5 and HIV severity: a prospective cohort study - Shujuan Yang; Chuanteng Feng; Teng Fei; Dan Wu; Liao Feng; Fengshun Yuan; Yao Fu; Hua Ma; Bin Yu; Li Liu; Yizhuo Li; Yiping Li; et al. (Science of The Total Environment, 2024)

Influence of aggregate characteristics on the plant growing environment of the planting concrete with SAC - Shanshan Jin; Yang Zhang; Yuling Yan; Zengmiao Xu; Aodong Li; Juan Wang; Pengfei Liu; Liuhuan Li; Zhihua Wang (Journal of Cleaner Production, 2024)

Soil moisture drives the response of soil microbial nutrient limitation to N and P additions in an Inner Mongolian meadow steppe - Hong Xiao; Yuping Rong; Pengzhen Li; Yuling Liu (European Journal of Soil Biology, 2024)

Association of short-term PM2.5 exposure with airway innate immune response, microbiota and metabolism alterations in human airways - Shuaiqi Zhao; Huijun Li; Fuyun Yang; Yishu Yang; Yuling Zeng; Zhen An; Juan Li; Hui Wu; Jie Song; Weidong Wu (Environmental Pollution, 2024)

Adaptive characteristics of indigenous microflora in an organically contaminated high salinity groundwater - Jili Wang; Yuling Zhang; Yang Ding; Yi Zhang; Weiqing Xu; Xinying Zhang; Yiliang Wang; Dong Li (Chemosphere, 2024)

Esketamine induces apoptosis of nasopharyngeal carcinoma cells through the PERK/CHOP pathway - Yuling Cao; Huiting Li; Yunfei Gao; Jiao Long; Lei Zheng; Qi Zhang; Ningning Li; Xinjin Chi (Toxicology and Applied Pharmacology, 2024)

Nitrogen and phosphorus additions alter foliar nutrient concentrations of dominant grass species and regulate primary productivity in an Inner Mongolian meadow steppe - Hong Xiao; Pengzhen Li; Thomas A. Monaco; Yuling Liu; Yuping Rong (Science of The Total Environment, 2024)

The hysteresis damage of cold exposure on tissue and transcript levels in mice - Jing Zhang; Shiwan You; Lan Yu; Yuling Zhang; Zuoping Li; Na Zhao; Bo Zhang; Lihua Kang; Shiguo Sun (Journal of Thermal Biology, 2024)

Plastic film mulching application improves potato yields, reduces ammonia emissions, but boosts the greenhouse gas emissions in China - Yalan Huang; Rongzhu Qin; Huihui Wei; Ning Chai; Yang Yang; Yuling Li; Pingxing Wan; Yufei Li; Wucheng Zhao; Siam Lawawirojwong; Tanita Suepa; Feng Zhang (Journal of Environmental Management, 2024)

Fabrication and characterization of polyvinyl alcohol/sodium alginate loaded carvacrol/silica hollow microspheres composite hydrogel as a colourimetric freshness indicator - Hongdan Hao; Bingchao Duan; Lidan Zhang; Lan Wang; Lingli Zhang; Yufei Wang; Yuanyuan Li; Chunmei Zhao; Guochao Jia; Yuling Li; Congjun Liu; Kui Lu (Food Bioscience, 2024)

Constructing 3D flower-like S-scheme N–Bi2O2CO3/g-C3N4 heterojunction with enhanced photocatalytic performance - Yong Huang; Mingliang Li; Xiaofang Zhang; Bo Xing; Yuling Ye; Ying Zeng (Environmental Research, 2024)

Eocene lacustrine microbialites in the western Qaidam Basin, China: implication for the sedimentary record and hydrocarbon potential - Xiang Li; Jiangong Wang; Guohui Long; Li Xu; Jun Cui; Xiujian Sun; Yuling Wang (Carbonates and Evaporites, 2024)

Lysosome-targeted ruthenium(II) complex encapsulated with pluronic® F-127 induces oncosis in A549 cells - Nanlian Pan; Yuqing Zhang; Minying Huang; Zhijun Liang; Yao Gong; Xide Chen; Yuling Li; Ciling Wu; Zunnan Huang; Jing Sun (JBIC Journal of Biological Inorganic Chemistry, 2024)

Exploring low-carbon mulching strategies for maize and wheat on-farm: Spatial responses, factors and mitigation potential - Huihui Wei; Kaiping Zhang; Ning Chai; Yue Wang; Yuling Li; Jianjun Yang; Matthew Tom Harrison; Ke Liu; Pingxing Wan; Wenjuan Zhang; Guojun Sun; Zhansheng Li; et al. (Science of The Total Environment, 2024)

Energy consumption and carbon emissions management in drinking water treatment plants: A systematic review - Mohamed Yateh; Fengting Li; Yuling Tang; Cheng Li; Bin Xu (Journal of Cleaner Production, 2024)

Distinctive interphasial properties and high structural reversibility endowed by B-/CN– electrolyte additive and its superior electrochemical performance for graphite/LiCoO2 pouch cells - Shuai Chen; Xinyang Wen; Yili Chen; Zhiyong Xia; Qiurong Chen; Lingling Huang; Haonan Huang; Haowen Pan; Yuling Fu; Jiarong He; Weishan Li (Chemical Engineering Journal, 2024)

Pd@HKUST-1@Cu(II)/CMC composite bead as an efficient synergistic bimetallic catalyst for Sonogashira cross-coupling reactions - Yuling Huang; Jiayi Huang; Yuping Zhou; Xuetao Fan; Yiqun Li (Carbohydrate Polymers, 2024)

Well-known polypeptides of deer antler velvet with key actives: modern pharmacological advances - He Sun; Dandan Xiao; Wei Liu; Xue Li; Zhe Lin; Yong Li; Yuling Ding (Naunyn-Schmiedeberg's Archives of Pharmacology, 2024)

The relationship between antidepressants and breast cancer: evidence from Mendelian randomization - Dong Niu; Chenchen Li; Xiaoyu Yan; Haoran Qu; Yuling Zheng (Cancer Causes & Control, 2024)
Background The use of antidepressants has increased over the years, but the relationship between antidepressant use and the risk of breast cancer is not uniform because of confounding factors. We aimed to assess the effect of antidepressants on breast cancer risk using a two-sample Mendelian randomization (MR) approach.stet Methods Secondary data analysis was performed on pooled data from genome-wide association studies based on single-nucleotide polymorphisms that were highly correlated with antidepressants, SSRI drugs, and serotonin and prolactin levels were selected as instrumental variables to evaluate the association between antidepressants and SSRI drugs and prolactin levels with breast cancer and ER+/ER- breast cancer. We then performed a test of the hypothesis that SSRI drugs elevate prolactin concentrations. We performed two-sample Mendelian randomization analyses using inverse variance weighting, MR-Egger regression, and weighted median methods, respectively. Results There was no significant risk association between antidepressant and SSRI use and the development of breast cancer, ER-positive or ER-negative breast cancer ( P > 0.05), and serotonin concentration was not associated with breast cancer risk ( P > 0.05). There was a positive causal relationship between prolactin levels and breast cancer (IVW, P = 0.02, OR = 1.058) and ER-positive breast cancer (Weighted median, P = 0.043, OR = 1.141; IVW, P = 0.009, OR = 1.125). Results in SSRI medication and prolactin levels showed no association between SSRI analogs and prolactin levels ( P > 0.05). Conclusion Large MR analysis showed that antidepressants as well as SSRI drugs were not associated with breast cancer risk and the SSRI-prolactin-breast cancer hypothesis did not hold in our analysis.

A biodegradable chitosan-based polymer for sustained nutrient release to stimulate groundwater hydrocarbon-degrading microflora - Jili Wang; Yuling Zhang; Ting Liu; Yujia Shi; Yang Ding; Yi Zhang; Weiqing Xu; Xinying Zhang; Yiliang Wang; Dong Li (Chemosphere, 2023)

Hydrothermal carbonization of biogas slurry and cattle manure into soil conditioner mitigates ammonia volatilization from paddy soil - Huiting Li; Detian Li; Shuhan Xu; Zhenqi Wang; Xu Chen; Yuling Ding; Qingnan Chu; Zhimin Sha (Chemosphere, 2023)

Establishment of evaluation system for biological remediation on organic pollution in groundwater using slow-release agents - Xinyue Du; Xiaoran Zhang; Junfeng Liu; Ziyang Zhang; Liyuan Wu; Xiaojuan Bai; Chaohong Tan; Yongwei Gong; Yuling Zhang; Haiyan Li (Science of The Total Environment, 2023)

Investigation on the mechanism of air/condensate bubble flotation of emulsified oil droplet - Ce Wang; Yuling Lü; Tianxu Ye; Li Chen; Limin He (Process Safety and Environmental Protection, 2023)

Transcriptome Analysis Reveals New Insights into the Respiration Metabolism Mechanism of Different Feeding Rations of Sea Cucumber (Apostichopus japonicus) - Yaoping Mei; Zhishuai Hou; Qinfeng Gao; Shuanglin Dong; Xueqi Li; Yuling Xu (Journal of Ocean University of China, 2023)

A chronostratigraphic and biostratigraphic framework for the Yanliao Biota of northeastern China: Implications for Jurassic terrestrial ecosystems and evolution - Yuling Li; Su-Chin Chang; Haichun Zhang; Jun Wang; Rui Pei; Daran Zheng; Yan Fang; Sidney R. Hemming (Palaeogeography, Palaeoclimatology, Palaeoecology, 2023)

New age constraints on the Lower Cretaceous Jiufengshan Formation of Inner Mongolia, China and their implications for the spatiotemporal development of the Jehol Biota - Yuling Li; Daran Zheng; Xiaobo Li; Xiao Teng; Qianqi Zhang; Han Wang; Hao-Yang Lee; Bo Wang; Su-Chin Chang (Palaeogeography, Palaeoclimatology, Palaeoecology, 2023)

Two 3D Ln(III)-MOFs Based on Phosphineoxide Ligand: Synthesis, Structure Luminescent and Photocatalytic Properties - Yuling Li; Kecheng Liu; Wenmin Zhang; Yingxin Wang; Baoyu Wang; Yufei Wang; Xiaochuan Li (Journal of Fluorescence, 2023)

Response characteristics of indigenous microbial community in polycyclic aromatic hydrocarbons (PAHs) contaminated aquifers under polyethylene microplastics stress: A microcosmic experimental study - Yang Ding; Jili Wang; Yuling Zhang; Yi Zhang; Weiqing Xu; Xinying Zhang; Yiliang Wang; Dong Li (Science of The Total Environment, 2023)

Relationship between carbon pool changes and environmental changes in arid and semi-arid steppe—A two decades study in Inner Mongolia, China - Hang Li; Banghui Yang; Yu Meng; Kai Liu; Shudong Wang; Dacheng Wang; Hongyan Zhang; Yuling Huang; Xingtao Liu; Dehui Li; Long Li; Xueke Li (Science of The Total Environment, 2023)

Calix[4]arene-based covalent organic frameworks with host-guest recognition for selective adsorption of six per- and polyfluoroalkyl substances in food followed by UHPLC-MS/MS detection - Zenghui Xie; Yuling Hu; Jiana Lin; Gongke Li; Qisheng Zhong (Journal of Hazardous Materials, 2023)

Straw removal or non-removal affects cadmium (Cd) accumulation in soil–rice (Oryza sativa L.) system at different ambient air Cd levels - Si Luo; Yuling Liu; Bihao Luo; Yihao Yang; Li Li; Xin Fu; Liang Peng; Qingru Zeng (Journal of Environmental Management, 2023)

Quantitative Assessment of Monitoring Natural Attenuation on Carbon Tetrachloride Reduction at a Groundwater-Contaminated Site in Eastern China - Yaqiang Wei; Weijiang Liu; Ling Liu; Haobo Niu; Lu Li; Yuling Chen; Jian Chen (Water, Air, & Soil Pollution, 2023)

Dkk-1–TNF-α crosstalk regulates MC3T3E1 pre-osteoblast proliferation and differentiation under mechanical stress through the ERK signaling pathway - Yeke Wu; Zheng Jing; Disi Deng; Jin Yan; Min Liu; Li Li; Yuling Zuo; Wenbin Wu; Qiongying Hu; Yunfei Xie (Molecular and Cellular Biochemistry, 2023)

Insights into electrogenerated intermediates and rapid screening of electrochemical reactions by surface-modified carbon fiber paper redox spray ionization mass spectrometry - Jiahui Bai; Mingmai Bao; Shanshan Wang; Tianlun Wen; Yuling Li; Jing Zhang; Tiansheng Mei; Yinlong Guo (Analytica Chimica Acta, 2023)

A dual-model immobilization-free photoelectrochemical/visual colorimetric bioanalysis based on microemulsion self-assemblies mediated multifunctional signal amplification strategy - Wenchao Geng; Linsheng Xue; Yuling Li; Jiangying Ji; Xinxin Yuan; Lihua Ding; Ruiying Yang (Analytica Chimica Acta, 2023)

Natural polysaccharide polymer network for sustained nutrient release to stimulate the activity of aromatic hydrocarbon-degrading indigenous microflora present in groundwater - Jili Wang; Yuling Zhang; Xi Wang; Siqi Yin; Ting Liu; Yujia Shi; Yang Ding; Yi Zhang; Weiqing Xu; Xinying Zhang; Yiliang Wang; Dong Li (Science of The Total Environment, 2023)

Intergenerational effects of parental [Cnmim]BF4 (n = 4, 6, 8) ionic liquids exposure on zebrafish development based on transcriptomic analysis - Yue Liu; Yanan Tian; Chenning Zhang; Xin Lu; Yuling Xue; Xinping Wang; Qiuyue Liao; Xin Li; Kai Lian; Jiaolong Huang; Jie Deng; Peng Duan (Science of The Total Environment, 2023)

Multiple fluorescence polymer dots-based differential array sensors for highly efficient heavy metal ions detection - Huanhuan Chen; Lvyang Zhu; Wenjun Jiang; Haiwei Ji; Xiaobo Zhou; Yuling Qin; Li Wu (Environmental Research, 2023)

Novel facile synthesis and room-temperature sintering of copper nanowires for solution-processed transparent conductive films - Qing Liu; Yibo Wu; Yong Li; Yuling Shi; Qianqian Pan; Danlong Yang; Tao Wang (Chemical Engineering Journal, 2023)

Manipulating polysulfide catalytic conversion through edge site construction, hybrid phase engineering, and Se anion substitution for kinetics-enhanced lithium-sulfur battery - Tong Li; Zhouhao Wang; Junping Hu; Haobin Song; Yuling Shi; Yu Jiang; Daohong Zhang; Shaozhuan Huang (Chemical Engineering Journal, 2023)

Genome-Wide Identification, Evolution Analysis of PI-PLC Family and Their Expression Patterns in Response to Different Hormones and Growth in Banana (Musa L.) - Qiuzhen Wu; Zhengyang Fan; Feng Qi; Dan Li; Zihao Zhang; Yukun Chen; Yuji Huang; Yuling Lin; Zhongxiong Lai (Tropical Plant Biology, 2023)

Rhizosphere soil keystone taxa of Robinia pseudoacacia and Juniperus sabina in an iron tailings matrix and their effects on soil enzyme activity - Xiaolin Chen; Haipeng Chen; Yuling Li (Plant and Soil, 2023)

Unveiling the characteristics of popcorn by genome re-sequencing and integrating the ESTs and proteome data - Yongbin Dong; Fei Deng; Long Zhang; Xinyu Li; Qilei Wang; Yuling Li (Cereal Research Communications, 2023)

Relationship between antigenicity and allergenic epitopes of extensive hydrolyzed whey protein: LC-MS/MS-based analysis - Ying Wang; Feifei Yang; Yao Zheng; Yuling Xue; Zhiyuan Kang; Justyna Zulewska; Hongjuan Li; Hongbo Li; Jinghua Yu (Food Bioscience, 2023)

A novel oral biomimetic delivery system enhancing both the mucosal and systemic immunity of influenza virus vaccine - Hongyan Lu; Yikun Gao; Jianmin Chen; Jing Chai; Ansheng Li; Tongtong Sun; Yuling Mao; Ye He; Qinfu Zhao; Jinghai Zhang; Siling Wang (Chemical Engineering Journal, 2023)

Mineral-microbial interactions in nine-year organic fertilization field experiment: a mechanism for carbon storage in saline-alkaline paddy soil - Mengmeng Chen; Yuling Zhang; Chunwei Gao; Shirong Zhang; Lu Liu; Lipeng Wu; Yuyi Li; Xiaodong Ding (Plant and Soil, 2023)

Performance test and effect evaluation of guar gum-stabilized loess as a sustainable slope protection material - Zhuolong Jia; Changgen Yan; Bo Li; Han Bao; Hengxing Lan; Zherui Liang; Yuling Shi; Jing Ren (Journal of Cleaner Production, 2023)

Dansyl-labelled cellulose as dual-functional adsorbents for elimination and detection of mercury in aqueous solution via aggregation-induced emission - Ming Li; Siqi Zhang; Panpan Zhang; Kexin Qin; Qian Chen; Qianyong Cao; Yuling Zhang; Jinghong Zhang; Chungang Yuan; Huining Xiao (Journal of Environmental Management, 2023)

Combustion and emission performance of a trapped-vortex gas turbine combustor fueled by RP-3 kerosene - Qian Wang; Mingyu Li; Yuling Zhao; Jiankun Xiao (Fuel, 2023)

Corrigendum to “Accumulation of dissolved organic matter in the transition from fresh to aged seasonal snow in an industrial city in NE China” [Sci. Total Environ. 857 (2023) 159337] - Zhen Mu; Xiaoying Niu; Christian George; Xinke Wang; Rujin Huang; Yuling Ma; Wei Pu; Yulin Qi; Pingqing Fu; Junjun Deng; Chao Ma; Nan Hu; et al. (Science of The Total Environment, 2023)

Boron doping g-C3N4 supported Cu2O for photocatalytic reforming of xylose into lactic acid - Yanting Lv; Weiyong Shao; Yuling Kong; Nanhua Li; Xinrui Huang; Zhihao Tang; Murong Gong; Lizi Li; Weiqi Wei (Journal of Environmental Chemical Engineering, 2023)

The effect of chlorfenapyr exposure on Solenopsis invicta Buren (Hymenoptera: Formicidae) - Yuling Liang; Mingrong Liang; Panpan Li; Yunbo Song; Yongyue Lu (Journal of Asia-Pacific Entomology, 2023)

Promotional role of Co on Cu-SAPO-34 towards enhanced denitration performance and SO2 tolerance - Yuling Zheng; Yangyang Mi; Yonglong Li; Wenming Liu; Daishe Wu; Yingying Zhang; Zhenguo Li; Honggen Peng (Fuel, 2023)

The effect of vacancy defective Mg (0001) surface on hydrogenation of Ni-Mg-CNTs: A mechanistic investigation - Congwen Duan; Mengmeng Wu; Xinya Wang; Dong Fu; Yuling Zhang; Wei Lv; Lianxi Hu; Ming Li; Fei Wang; Ying Wu (Fuel, 2023)

Effects of a novel plant growth regulator B2 on stalk quality and grain yield of winter wheat in North China - Chuanxi Peng; Yuling Guo; Guanmin Huang; Yingru Liu; Zhaohu Li; Yuyi Zhou; Liusheng Duan (Plant and Soil, 2023)

Larvicidal, acetylcholinesterase inhibitory activities of four essential oils and their constituents against Aedes albopictus, and nanoemulsion preparation - Yuling Li; Weifeng Wu; Rongchao Jian; Xiaofei Ren; Xiaole Chen; Weiqian David Hong; Min Wu; Jinglin Cai; Canyao Lao; Ximing Xu; Zhaojun Sheng (Journal of Pest Science, 2023)

The miR156x + p/SPL13-6 module responds to ABA, IAA, and ethylene, and SPL13-6 participates in the juvenile–adult phase transition in Pyrus - Minyan Song; Anqi Li; Lei Sun; Yuling Mei; Zhiyan Wang; Rihong Wang; Ran Wang; Dingli Li; Jiankun Song; Chunxiang Zhang; Yingjie Yang (Horticulture, Environment, and Biotechnology, 2023)

Coconut shell biochar application in liquid-solid microextraction of triazine herbicides from multi-media environmental samples - Mengge Ma; Zongliang Niu; Zhuhua Tang; Jinyang Bai; Bei Li; Yuling Zhou; Yingying Wen (Analytica Chimica Acta, 2023)

Offshore-onshore tectonomagmatic correlations: Towards a Late Mesozoic non-Andean-type Cathaysian continental margin - Changhai Xu; Yuling Deng; Calvin G. Barnes; Hesheng Shi; Christophe Pascal; Yuanyuan Li; Shunli Gao; Donghui Jiang; Jianlei Xie; Changqian Ma (Earth-Science Reviews, 2023)

Remediation of atrazine-contaminated soil in a fluidized-bed DBD plasma reactor - Nan Jiang; Ying Qu; Jinwei Zhu; Hongchang Wang; Ju Li; Yun Shu; Yutao Cui; Yuling Tan; Bangfa Peng; Jie Li (Chemical Engineering Journal, 2023)

The cotton pectin methyl esterase gene GhPME21 functions in microspore development and fertility in Gossypium hirsutum L. - Yihan Xu; Yanhua Jiang; Junye Jiao; Hongli Zheng; Yuqing Wu; Yuling Li; Rayhangul Abdursul; Yanyan Zhao; Liping Ke; Yuqiang Sun (Plant Molecular Biology, 2023)

Fungicide exposure accelerated horizontal transfer of antibiotic resistance genes via plasmid-mediated conjugation - Houpu Zhang; Jiajin Song; Zhiruo Zheng; Tongxin Li; Nan Shi; Yuling Han; Luqing Zhang; Yunlong Yu; Hua Fang (Water Research, 2023)

How efficient is the environmental pollution control in China? - Ke Guo; Zhengyang Li; Yuequn Cao; Yuling Yang (Process Safety and Environmental Protection, 2023)

Inhibition mechanisms of urea combined with nitrification on cadmium uptake by rice (Oryza sativa L.) seedlings - Li Li; Yuling Liu; Shijing Zhang; Siduo Ding; Xin Fu; Qingru Zeng; Liang Peng; Si Luo (Plant and Soil, 2023)

Social carrying capacity and emotion dynamics in urban national parks during the COVID-19 pandemic - Xiao Xiao; Jie Gao; Junyu Lu; Peizhe Li; Yuling Zhang (Journal of Outdoor Recreation and Tourism, 2023)

Large-scale metabolome analysis reveals dynamic changes of metabolites during foxtail millet grain filling - Tao Wang; Lu Xing; Hui Song; Yangyang Wei; Pengtao Li; Quanwei Lu; Nan Hu; Yuling Liu; Yongqing Zhao; Jinrong Liu; Baohong Zhang; Renhai Peng (Food Research International, 2023)

A negative-response strain sensor towards wearable microclimate changes for body area sensing networks - Jing Liu; Junze Zhang; Zeyu Zhao; Yanping Liu; Wai Cheong Tam; Zhaozhu Zheng; Xiaoqin Wang; Yuling Li; Zekun Liu; Yi Li; Gang Li (Chemical Engineering Journal, 2023)

GRK5 Deficiency in the Hippocampus Leads to Cognitive Impairment via Abnormal Microglial Alterations - Hongtao Shen; Tianzhen Zhang; Yao Ji; Yu Zhang; Yongxiang Wang; Yuling Jiang; Xiongjin Chen; Qiuhao Liang; Kefeng Wu; Yunfeng Li; Xingyu Lu; Lili Cui; et al. (Molecular Neurobiology, 2023)

Pollution in river tributaries restricts the water quality of ecological water replenishment in the Baiyangdian watershed, China - Xu Yao; Zheng Wang; Wei Liu; Yao Zhang; Tianhe Wang; Yuling Li (Environmental Science and Pollution Research, 2023)

Effects of probiotics, prebiotics, and synbiotics on polycystic ovary syndrome: a systematic review and meta-analysis - Yuling Li; Yong Tan; Guicheng Xia; Jiaqi Shuai (Critical Reviews in Food Science and Nutrition, 2023)

The increased medical burden associated with frailty is partly attributable to household solid fuel: A nationwide prospective study of middle-aged and older people in China - Xiaoyu Jin; Yuling Wang; Yudong Wu; Yunfeng Liang; Yuxuan Li; Xiaoni Sun; Shuangshuang Yan; Lu Mei; Junwen Tao; Jian Song; Rubing Pan; Weizhuo Yi; et al. (Science of The Total Environment, 2023)

Water deficit aggravated the inhibition of photosynthetic performance of maize under mercury stress but is alleviated by brassinosteroids - Yulou Tang; Junjie Zhang; Lijuan Wang; Hao Wang; Haochi Long; Liuyang Yang; Gengwei Li; Jiameng Guo; Yongchao Wang; Yuling Li; Qinghua Yang; Weiyu Shi; et al. (Journal of Hazardous Materials, 2023)

Mechanism of thermally activated sodium persulfate–biochar skeleton treatment to improve the dewaterability of waste activated sludge - Shuaishuai Li; Yuling Liu; Chuanchuan Dou; Ruihao Sun (Journal of Environmental Chemical Engineering, 2023)

Hyperspectral imaging combined with chemometrics for rapid detection of talcum powder adulterated in wheat flour - Hong-Ju He; Yan Chen; Guanglei Li; Yuling Wang; Xingqi Ou; Jingli Guo (Food Control, 2023)

A newly developed consortium with a highly efficient thiocyanate degradation capacity: A comprehensive investigation of the degradation and detoxification potential - Xiaoshuang Xiao; Xuejiao An; Yuling Jiang; Liuwei Wang; Zelin Li; Fenju Lai; Qinghua Zhang (Environmental Pollution, 2023)

Spatial Structure of China’s E-commerce Express Logistics Network Based on Space of Flows - Yuanjun Li; Qitao Wu; Yuling Zhang; Guangqing Huang; Hongou Zhang (Chinese Geographical Science, 2023)

Novel sensor array distinguishes heavy metal ions based on multiple fluorescence channels from dendritic mesoporous silica nanoparticles - Xiaotong Wu; Lei Tan; Yuling Li; Wanqiong Liu; Zhihua Peng; Yanshan Dong; Zeyu Huang; Lin Zhang; Yong Liang (Analytica Chimica Acta, 2023)

Atmospheric particulate matter impairs cognition by modulating synaptic function via the nose-to-brain route - Chunmei Liang; Yuling Jiang; Tianzhen Zhang; Yao Ji; Yu Zhang; Yuanhong Sun; Shengnan Li; Yi Qi; Yan Wang; Yujie Cai; Tianwen Lai; Lili Cui (Science of The Total Environment, 2023)

Toxicity of ceria nanoparticles to the regeneration of freshwater planarian Dugesia japonica: The role of biotransformation - Changjian Xie; Xiaowei Li; Lisha Hei; Yiqing Chen; Yuling Dong; Shujing Zhang; Shan Ma; Jianing Xu; Qiuxiang Pang; Iseult Lynch; Zhiling Guo; Peng Zhang (Science of The Total Environment, 2023)

Four decades of hydrological response to vegetation dynamics and anthropogenic factors in the Three-North Region of China and Mongolia - Dehui Li; Kai Liu; Shudong Wang; Taixia Wu; Hang Li; Yong Bo; Hongyan Zhang; Yuling Huang; Xueke Li (Science of The Total Environment, 2023)

Accumulation of dissolved organic matter in the transition from fresh to aged seasonal snow in an industrial city in NE China - Zhen Mu; Xiaoying Niu; Christian George; Xinke Wang; Rujin Huang; Yuling Ma; Wei Pu; Yulin Qi; Pingqing Fu; Junjun Deng; Chao Ma; Nan Hu; et al. (Science of The Total Environment, 2023)

Efficient determination of enantiomeric ratios of α-hydroxy/amino acids from fermented milks via ion mobility−mass spectrometry - Yuling Li; Li Zhang; Wenjian Sun; Kuofeng Tseng; Jing Zhang; Yinlong Guo (Food Chemistry, 2023)

Effective enrichment and detection of bisphenol diglycidyl ether, novolac glycerol ether and their derivatives in canned food using a novel magnetic sulfonatocalix[6]arene covalent cross-linked polymer as the adsorbent - Zenghui Xie; Yuling Hu; Yanlong Chen; Gang Wu; Gongke Li; Qisheng Zhong (Food Chemistry, 2023)

Experimental study on adsorption removal of SO2 in flue gas by defective UiO-66 - Yuling Ma; Airong Li; Cheng Wang (Chemical Engineering Journal, 2023)

Achieving highly efficient near-ultraviolet emitters via optimizing molecular configuration by the intramolecular-locked donor and acceptor - Daokun Zhong; Xiaolong Yang; Xuming Deng; Xi Chen; Yuling Sun; Peng Tao; Zikang Li; Jie Zhang; Guijiang Zhou; Wai-Yeung Wong (Chemical Engineering Journal, 2023)

The reaction mechanism of highly dispersed Cu atoms and ultrafine MnOx nanoclusters co-modified ZSM-5 based on in-situ heteronuclear substitution for catalytic oxidation C6H14 - Jian Li; Jingnan Hu; Yingjie Shi; Jiajia Zhao; Hongchang Wang; Shuang Deng; Yutao Cui; Fan Wang; Hongyan Long; Yuling Tan (Chemical Engineering Journal, 2023)

Projecting extreme climate events in China’s Loess Plateau: multiple RCMs and emission scenarios corrected by a trend-preserving method - Yuling Ren; Jingpeng Zhang; Bingbing Li; Jinxia Fu; Zhi Li (Theoretical and Applied Climatology, 2023)

Bacterial community structure and diversity in the rhizospheric soil of Robinia pseudoacacia and Juniperus sabina planted in iron tailings matrix - Xiaolin Chen; Haipeng Chen; Jiaqi Zhao; Yue Xin; Yuling Li (Environmental Science and Pollution Research, 2022)

Spatiotemporally varied extreme precipitation events simultaneously controlled by multiple circulation factors in China's Loess Plateau - Yuling Ren; Jingpeng Zhang; Jinxia Fu; Shouzhang Peng; Zhi Li (International Journal of Climatology, 2022)
The intensive and frequent extreme precipitation events (EPE) greatly contribute to the severe soil loss in China's Loess Plateau, and it is thus essential to understand how and why EPE varies with space and time. Particularly, the combined influence of multiple factors on EPE has rarely been explored. This study analysed the spatiotemporal variability of EPE for 1961–2017 after defining six indices for intensity, frequency, and duration of EPE (R5d, SDII, R90t, R90n, CDD, CWD). We employed 12 atmospheric circulation factors to determine their combined effects on EPE on different time scales over time by the multiple wavelet coherence. The EPE indices spatially varied with obvious southeast‐northwest gradients. Averaged across the whole plateau, SDII, R90t, and R90n increased insignificantly, while R5d, CDD, and CWD decreased insignificantly. In addition, the change trend had spatial variations with most wet EPE indices increasing in the north and the southernmost areas and decreasing in the middle‐south areas. SDII, R90t, and R90n at 68%, 66%, and 53% of stations tended to increase, respectively, and R5d, CDD, and CWD decreased at 66%, 70%, and 77% of stations, respectively. The temperature had a greater correlation with the duration of EPE in summer and on the intensity and frequency of EPE in winter. El Niño‐Southern Oscillation (ENSO), Pacific North American teleconnection pattern (PNA), ENSO‐Arctic Oscillation (AO), and ENSO‐AO‐PNA were found to be the main factors influencing EPE individually or simultaneously. This study provides technical support for the identification of combined effects of multiple factors, and the results are helpful for regional environmental management. Specific to the Loess Plateau, the identified individual or multiple factors can be used to project future changes in EPE, and the more frequent and intensive EPE in some regions may increase the difficulty in future soil loss control.

PAH-induced metabolic changes related to inflammation in childhood asthma - Hao Wu; Yuling Bao; Tongtong Yan; Hui Huang; Ping Jiang; Zhan Zhang; Lei Li; Qian Wu (Environmental Science and Pollution Research, 2022)

Effects of different stocking densities on the CO2 fluxes at water-air interface and the respiration metabolism in sea cucumber Apostichopus japonicus (Selenka) - Yaoping Mei; Yuan Tian; Qinfeng Gao; Shuanglin Dong; Xueqi Li; Yuling Xu (Frontiers in Marine Science, 2022)
Recently, abundant research has been devoted to investigating the variations of CO 2 concentration in the atmosphere. However, the information of CO 2 fluxes at the water-air interface remains limited, especially those from the respiratory metabolism of aquatic organisms. In the present study, a comprehensive analysis was carried out to evaluate the effects of different stocking densities of sea cucumber ( Apostichopus japonicus ) on the CO 2 fluxes at water-air interface, and to explore the relationships between CO 2 fluxes and respiratory metabolism. A total of 60 sea cucumbers were randomly classified into 4 groups with different stocking densities, including 2, 5 and 8 ind./tank (namely D2, D5 and D8 groups). After 34-day feeding trial, individuals in D5 had superior growth performance rather than D2 and D8. The analysis of modified floating static chambers clearly showed that the mean CO 2 flux at the water-air interface in D5 was significantly higher than D2 and D8. Meanwhile, energy budget analysis revealed that D5 had higher carbon and nitrogen utilization, excretion energy and metabolizable energy, suggesting relatively active respiration metabolism in moderate stocking density. The activities of pyruvate dehydrogenase (PDH) and α-ketoglutarate dehydrogenase (OGDH) in respiratory tree and body wall tissues provided additional evidence for the higher respiration metabolism rate of individuals at D5, which may be responsible for the higher CO 2 fluxes at the water-air interface. Transcriptome analysis was performed to uncover the molecular mechanism of respiratory metabolism affected by different stocking densities. The differentially expressed genes in respiration trees and body walls were significantly enriched in peroxisome, fatty acid degradation, and oxidative phosphorylation pathways. It may explain the differences of respiration metabolism rates at different stocking densities. The present study preliminarily revealed the CO 2 fluxes variation at the water-air interface from aquatic invertebrates, and provided the scientific basis for the efficient and low-carbon agricultural technologies of sea cucumber.

Activation of cadmium under simulated solar illumination and its impact on the mobility of Cd in flooded soils - Bihao Luo; Chenfeng Xiao; Yuling Liu; Li Li; Liang Peng; Qingru Zeng; Si Luo (Environmental Science and Pollution Research, 2022)

Preparation of formate-free PMA@MOF-808 catalysts for deep oxidative desulfurization of model fuels - Cheng Wang; Airong Li; Yuling Ma; Shenglan Qing (Environmental Science and Pollution Research, 2022)

Research on Transfer Rate of Heavy Metals and Harmful Elements in Traditional Chinese Medicine Extraction and Refining Processes and Product Health Risk Assessment - Dujia Jin; Lin Li; Wujun Dong; Xiangyang Zhu; Xuejun Xia; Renyun Wang; Jun Ye; Ran Li; Zhihua Liu; Xueqing Xu; Lili Gao; Yuling Liu; et al. (Biological Trace Element Research, 2022)

The importance of compound-specific radiocarbon analysis in source identification of polycyclic aromatic hydrocarbons: A critical review - Miaolei Ya; Yuling Wu; Xinhong Wang; Yongyu Li; Guanyong Su (Critical Reviews in Environmental Science and Technology, 2022)

Persistence of Digestive Enzyme Activities of Sea Cucumber (Apostichopus japonicus): Evidence From Diet Switch After Evisceration - Xueqi Li; Qinfeng Gao; Yuan Tian; Yaoping Mei; Yuling Xu; Yiming Cao; Shuanglin Dong; Yangen Zhou; Yongjun Sun; Wenming Ju (Frontiers in Marine Science, 2022)
A two-stage diet-switch experiment was conducted to examine the hypothesis that the changes in digestive enzyme activities of sea cucumber ( Apostichopus japonicus ) induced by historic diets might persist in the regenerated intestines. In stage I, A. japonicus were treated with two different diets for 56 days, including diet A with 11% crude protein, 1% crude lipid, and 40% carbohydrate, and diet B with 18% crude protein, 2% crude lipid, and 35% carbohydrate. In stage II, each treatment was subjected to evisceration with 0.35M KCl or not (eviscerated and non-eviscerated groups), half of which were then switched to different diets from diet A to B or vice versa for 112 days. The persistence of digestive enzyme activities was evaluated by measuring the changes in digestive enzyme activities before and after evisceration. In stage I, diets B and A increased trypsin and amylase activities, respectively. In stage II, the higher trypsin activities were observed in eviscerated and non-eviscerated A. japonicus that had consumed diet B in stage I. The higher amylase activities were observed only in eviscerated A. japonicus that had consumed diet A in stage I. It indicated that the historic diets showed long-term effects on the digestion of A. japonicus , which led to the persistence of changes in both trypsin and amylase activities in intestines, especially in the regenerated intestines. In addition, the specific growth rates (SGRs) and metabolic rates (MRs) of A. japonicus were affected by the long-term effects of historic diets. Meanwhile, the relationships between enzymic activities, SGRs, and MRs were observed in A. japonicus , indicating that the historic diets could produce long-term effects on the growth and metabolism of A. japonicus through their long-term effects of historic diets on digestive enzyme activities. In conclusion, the present study showed that the changes in digestive enzyme activities induced by different diets in stage I could persist in the intestines and regenerated intestines, leading to long-term effects of historic diets on the growth and metabolism of A. japonicus .

A review on submarine oil and gas leakage in near field: droplets and plume - Qiuyan Wang; Yuling Lü; Qigui Li (Environmental Science and Pollution Research, 2022)

Effects of Supplementary Selenium and Vitamin E on the Growth Performance, Antioxidant Enzyme Activity, and Gene Expression of Sea Cucumber Apostichopus japonicus - Yuling Xu; Qinfeng Gao; Shuanglin Dong; Yaoping Mei; Xueqi Li (Biological Trace Element Research, 2021)

The relationship between job stress and job burnout moderated by BDNF rs6265 polymorphism - Haiying Jia; Mingwei He; Xiaoyue Zhang; Yuling Li; Shu-chang He; Xiang-Yang Zhang (Psychopharmacology, 2021)

Plant multiscale networks: charting plant connectivity by multi-level analysis and imaging techniques - Xi Zhang; Yi Man; Xiaohong Zhuang; Jinbo Shen; Yi Zhang; Yaning Cui; Meng Yu; Jingjing Xing; Guangchao Wang; Na Lian; Zijian Hu; Lingyu Ma; et al. (Science China Life Sciences, 2021)

The comparative impact among different intensive statins and combination therapies with niacin/ezetimibe on carotid intima-media thickness: a systematic review, traditional meta-analysis, and network meta-analysis of randomized controlled trials - Hongwei Li; Xiaolin Xu; Liming Lu; Runlu Sun; Qi Guo; Qian Chen; Junjie Wang; Zhijian He; Yuling Zhang (European Journal of Clinical Pharmacology, 2021)

Protective effects of SP600125 on mice infected with H1N1 influenza A virus - Yuling Tang; Guanghui Yang; Yuxiang Li; Ming Wang; Gebin Li; Yanxin Hu (Archives of Virology, 2021)

Genetic Architecture of Childhood Kidney and Urological Diseases in China - Ye Fang; Hua Shi; Tianchao Xiang; Jiaojiao Liu; Jialu Liu; Xiaoshan Tang; Xiaoyan Fang; Jing Chen; Yihui Zhai; Qian Shen; Guomin Li; Li Sun; et al. (Phenomics, 2021)
Kidney disease is manifested in a wide variety of phenotypes, many of which have an important hereditary component. To delineate the genotypic and phenotypic spectrum of pediatric nephropathy, a multicenter registration system is being implemented based on the Chinese Children Genetic Kidney Disease Database (CCGKDD). In this study, all the patients with kidney and urological diseases were recruited from 2014 to 2020. Genetic analysis was conducted using exome sequencing for families with multiple affected individuals with nephropathy or clinical suspicion of a genetic kidney disease owing to early-onset or extrarenal features. The genetic diagnosis was confirmed in 883 of 2256 (39.1%) patients from 23 provinces in China. Phenotypic profiles showed that the primary diagnosis included steroid-resistant nephrotic syndrome (SRNS, 23.5%), glomerulonephritis (GN, 32.2%), congenital anomalies of the kidney and urinary tract (CAKUT, 21.2%), cystic renal disease (3.9%), renal calcinosis/stone (3.6%), tubulopathy (9.7%), and chronic kidney disease of unknown etiology (CKDu, 5.8%). The pathogenic variants of 105 monogenetic disorders were identified. Ten distinct genomic disorders were identified as pathogenic copy number variants (CNVs) in 11 patients. The diagnostic yield differed by subgroups, and was highest in those with cystic renal disease (66.3%), followed by tubulopathy (58.4%), GN (57.7%), CKDu (43.5%), SRNS (29.2%), renal calcinosis /stone (29.3%) and CAKUT (8.6%). Reverse phenotyping permitted correct identification in 40 cases with clinical reassessment and unexpected genetic conditions. We present the results of the largest cohort of children with kidney disease in China where diagnostic exome sequencing was performed. Our data demonstrate the utility of family-based exome sequencing, and indicate that the combined analysis of genotype and phenotype based on the national patient registry is pivotal to the genetic diagnosis of kidney disease.

Maize Straw Deep-Burying Promotes Soil Bacteria Community Abundance and Improves Soil Fertility - Jiaqi Li; Xuhong Ye; Yuling Zhang; Ji Chen; Na Yu; Hongtao Zou (Journal of Soil Science and Plant Nutrition, 2021)

Whether foreign direct investment can promote high-quality economic development under environmental regulation: evidence from the Yangtze River Economic Belt, China - Xiaosheng Li; Yuling Lu; Ruting Huang (Environmental Science and Pollution Research, 2021)

Correction to: The Preliminary Study on the Association Between PAHs and Air Pollutants and Microbiota Diversity - Jinye Hu; Yuling Bao; Yuqi Zhu; Ranagul Osman; Mengfan Shen; Zhan Zhang; Li Wang; Shuyuan Cao; Lei Li; Qian Wu (Archives of Environmental Contamination and Toxicology, 2021)

TMEM166 inhibits cell proliferation, migration and invasion in hepatocellular carcinoma via upregulating TP53 - Jiejie Yang; Bin Wang; Qian Xu; Yuling Yang; Lin Hou; Kan Yin; Qingming Guo; Yanan Hua; Li Zhang; Yixuan Li; Jinyu Zhang; Ning Li (Molecular and Cellular Biochemistry, 2021)

Analysis of microbial community structure and degradation of ammonia nitrogen in groundwater in cold regions - Shuo Li; Yuling Zhang; Siqi Yin; Xi Wang; Ting Liu; Zhiqun Deng (Environmental Science and Pollution Research, 2020)

Inhibition of berberine hydrochloride on Candida albicans biofilm formation - Xiaoxue Huang; Mingyue Zheng; Yuling Yi; Anamica Patel; Zhen Song; Yan Li (Biotechnology Letters, 2020)

The Preliminary Study on the Association Between PAHs and Air Pollutants and Microbiota Diversity - Jinye Hu; Yuling Bao; Yuqi Zhu; Ranagul Osman; Mengfan Shen; Zhan Zhang; Li Wang; Shuyuan Cao; Lei Li; Qian Wu (Archives of Environmental Contamination and Toxicology, 2020)

Macrophage-Derived Extracellular Vesicles as Drug Delivery Systems for Triple Negative Breast Cancer (TNBC) Therapy - Matthew J. Haney; Yuling Zhao; Yeon S. Jin; Samuel M. Li; Juli R. Bago; Natalia L. Klyachko; Alexander V. Kabanov; Elena V. Batrakova (Journal of Neuroimmune Pharmacology, 2020)

Inhibitory effects of Dulcitol on rat C6 glioma by regulating autophagy pathway - Yuling Zhang; Hui Wang; Fangjuan Li; Xinxin Xu; Baogui Chen; Tao Zhang (Natural Product Research, 2020)

Effects of iron, calcium, and organic matter on phosphorus behavior in fluvo-aquic soil: farmland investigation and aging experiments - Yuling Ma; Jie Ma; Hao Peng; Liping Weng; Yali Chen; Yongtao Li (Journal of Soils and Sediments, 2019)

Impacts of Large-Area Impervious Surfaces on Regional Land Surface Temperature in the Great Pearl River Delta, China - Yuling Ma; Kun Yang; Shaohua Zhang; Mingchan Li (Journal of the Indian Society of Remote Sensing, 2019)

Preparation, Characterization, and Properties of Inclusion Complexes of Balofloxacin with Cyclodextrins - Xiuyun Ren; Hongyun Qian; Peixiao Tang; Yuling Tang; Yuanyuan Liu; Hongyu Pu; Man Zhang; Ludan Zhao; Hui Li (AAPS PharmSciTech, 2019)

Effects of deficit irrigation combined with rainwater harvesting planting system on the water use efficiency and maize (Zea mays L.) yield in a semiarid area - Peng Zhang; Ting Wei; Yuling Li; Yan Zhang; Tie Cai; Xiaolong Ren; Qingfang Han; Zhikuan Jia (Irrigation Science, 2019)

Abnormal Brain Structure and Function in First-Episode Childhood- and Adolescence-Onset Schizophrenia: Association with Clinical Symptoms - Yanhong Xia; Dan Lv; Yinghui Liang; Haisan Zhang; Keyang Pei; Rongrong Shao; Yali Li; Yan Zhang; Yuling Li; Jinghua Guo; Luxian Lv; Suqin Guo (Neuroscience Bulletin, 2019)

D-RADA16-RGD-Reinforced Nano-Hydroxyapatite/Polyamide 66 Ternary Biomaterial for Bone Formation - WeiKang Zhao; Bin He; Ao Zhou; Yuling Li; Xiaojun Chen; Qiming Yang; Beike Chen; Bo Qiao; Dianming Jiang (Tissue Engineering and Regenerative Medicine, 2019)

Spatiotemporal Change of Sparse Vegetation Coverage in Northern China - Lili Feng; Zhiqing Jia; Qingxue Li; Anzhou Zhao; Yuling Zhao; Zhaojiang Zhang (Journal of the Indian Society of Remote Sensing, 2019)

Spatiotemporal Change of Aeolian Desertification Land Distribution in Northern China from 2001 to 2015 - Lili Feng; Zhiqing Jia; Qingxue Li; Anzhou Zhao; Zhaojiang Zhang; Yuling Zhao (Journal of the Indian Society of Remote Sensing, 2018)

Synthesis, Characterization and Luminescent Properties of Anthracen- or Pyrene-Based Coumarin Derivatives - Hui Zhang; Li Zhao; Qinglong Luo; Yuling Zhao; Tianzhi Yu (Journal of Fluorescence, 2018)

Exogenous salicylic acid regulates reactive oxygen species metabolism and ascorbate–glutathione cycle in Nitraria tangutorum Bobr. under salinity stress - Yongqing Yan; Chenhui Pan; Yuling Du; Danyang Li; Wei Liu (Physiology and Molecular Biology of Plants, 2018)

Molecular cloning and characterization of squalene synthase from Matricaria recutita L. - Xiaojuan Hou; Yuling Tai; Shuping Ling; Dahui Li; Chunxiao Guo; Jiameng Sun; Guifang Pan; Yi Yuan (Acta Physiologiae Plantarum, 2018)

Selection of a Ligand-Binding Neutralizing Antibody Assay for Benralizumab: Comparison with an Antibody-Dependent Cell-Mediated Cytotoxicity (ADCC) Cell-Based Assay - Yuling Wu; Ahmad Akhgar; Jia J Li; Binbing Yu; Cecil Chen; Nancy Lee; Wendy I. White; Lorin K. Roskos (The AAPS Journal, 2018)

Determination and optimization of a strong promoter element from Bacillus amyloliquefaciens by using a promoter probe vector - Yuling Liao; Bin Wang; Yanrui Ye; Li Pan (Biotechnology Letters, 2018)

Optimization of the purine operon and energy generation in Bacillus amyloliquefaciens for guanosine production - Yuling Liao; Yanrui Ye; Bin Wang; Li Pan (Biotechnology Letters, 2017)

Chest circumference and birth weight are good predictors of lung function in preschool children from an e-waste recycling area - Xiang Zeng; Xijin Xu; Yuling Zhang; Weiqiu Li; Xia Huo (Environmental Science and Pollution Research, 2017)

Optimization of Lipid Extraction and Determination of Fatty Acid Compositions in Edible Meats of Freshwater and Marine Shrimps - Li Zhou; Peixuan Li; Yuling Zhao; Shuang Hou; Baolei Cong; Jun Huang; Yu Ding; Xiaoxiong Zeng (Journal of Aquatic Food Product Technology, 2017)

Construction and characterization of a bacterial artificial chromosome library for Camellia sinensis - Yuling Tai; Hao Wang; Chaoling Wei; Ling Su; Min Li; Liqun Wang; Zhaozhao Dai; Lingyun Shao; Jiayue Jiang; Meizhong Luo; Hua Yang; Weiwei Deng; et al. (Tree Genetics & Genomes, 2017)

Verification and fine mapping of qGW1.05, a major QTL for grain weight in maize (Zea mays L.) - Qiang Zhou; Yongbin Dong; Qingling Shi; Long Zhang; Huanqing Chen; Chunhui Hu; Yuling Li (Molecular Genetics and Genomics, 2017)

Polybrominated diphenyl ethers, organochlorine pesticides, and polycyclic aromatic hydrocarbons in water from the Jiulong River Estuary, China: levels, distributions, influencing factors, and risk assessment - Yuling Wu; Xinhong Wang; Yongyu Li; Miaolei Ya; Hui Luo; Huasheng Hong (Environmental Science and Pollution Research, 2017)

Effects of seawater acidification on the growth rates of the diatom Thalassiosira (Conticribra) weissflogii under different nutrient, light, and UV radiation regimes - Wei Li; Yuling Yang; Zhenzhen Li; Juntian Xu; Kunshan Gao (Journal of Applied Phycology, 2017)

Remediation of Cr(VI)-Contaminated Soil Using the Acidified Hydrazine Hydrate - Yameng Ma; Fangfang Li; Yuling Jiang; Weihua Yang; Lv Lv; Haotian Xue; Yangyang Wang (Bulletin of Environmental Contamination and Toxicology, 2016)

Ectopic expression of the maize ZmADF3 gene in Arabidopsis revealing its functions in kernel development - Dahe Qiao; Yongbin Dong; Long Zhang; Qiang Zhou; Chunhui Hu; Yangliu Ren; Yuling Li (Plant Cell, Tissue and Organ Culture (PCTOC), 2016)

Characterization of a maize ERF gene, ZmERF1, in hormone and stress responses - Qingling Shi; Yongbin Dong; Qiang Zhou; Dahe Qiao; Zhiyan Ma; Long Zhang; Yuling Li (Acta Physiologiae Plantarum, 2016)

Detecting land uplift associated with enhanced oil recovery using InSAR in the Karamay oil field, Xinjiang, China - Lingyun Ji; Yong Zhang; Qingliang Wang; Yuling Xin; Jin Li (International Journal of Remote Sensing, 2016)

A New Star-shaped Carbazole Derivative with Polyhedral Oligomeric Silsesquioxane Core: Crystal Structure and Unique Photoluminescence Property - Zixuan Xu; Tianzhi Yu; Yuling Zhao; Hui Zhang; Guoyun Zhao; Jianfeng Li; Lanqin Chai (Journal of Fluorescence, 2016)

Effects of epigallocatechin gallate on the cell-wall structure of Mycobacterial smegmatis mc 2 155 - Tieying Sun; Biaojie Qin; Mingchuan Gao; Yuling Yin; Changyuan Wang; Shizhu Zang; Xinli Li; Cuili Zhang; Yi Xin; Tao Jiang (Natural Product Research, 2015)

A Neutralizing Antibody Assay Based on a Reporter of Antibody-Dependent Cell-Mediated Cytotoxicity - Yuling Wu; Jia J. Li; Hyun Jun Kim; Xu Liu; Weiyi Liu; Ahmad Akhgar; Michael A. Bowen; Susan Spitz; Xu-Rong Jiang; Lorin K. Roskos; Wendy I. White (The AAPS Journal, 2015)

Physiological and biochemical responses and microscopic structure changes of Populus tomentosa Carr seedlings to 4-BDE exposure - Man Cai; Yuling Li; Yanling Li; Kejiu Du (Environmental Science and Pollution Research, 2015)

QTL identification and meta-analysis for kernel composition traits across three generations in popcorn - Yongbin Dong; Zhongwei Zhang; Qingling Shi; Qilei Wang; Qiang Zhou; Yuling Li (Euphytica, 2015)

Association between blood erythrocyte lead concentrations and hemoglobin levels in preschool children - Chunhua Liu; Xia Huo; Peng Lin; Yuling Zhang; Weiqiu Li; Xijin Xu (Environmental Science and Pollution Research, 2015)

Statures in Han populations of China - LianBin Zheng; YongLan Li; HuanJiu Xi; KeLi Yu; ShunHua Lu; Rui Shi; YouFeng Wen; JingPing Bao; XingHua Zhang; YuLing Li; Fu Ren; GuoChang Xu (Science China Life Sciences, 2015)

Isolation and characterization of ZmERF1 encoding ethylene responsive factor-like protein 1 in popcorn (Zea mays L.) - Qingling Shi; Yongbin Dong; Dahe Qiao; Qilei Wang; Zhiyan Ma; Feifei Zhang; Qiang Zhou; He Xu; Fei Deng; Yuling Li (Plant Cell, Tissue and Organ Culture (PCTOC), 2015)

Phylogeography and evolution of a fungal–insect association on the T ibetan P lateau - Yongjie Zhang; Shu Zhang; Yuling Li; Shaoli Ma; Chengshu Wang; Meichun Xiang; Xin Liu; Zhiqiang An; Jianping Xu; Xingzhong Liu (Molecular Ecology, 2014)
Parasitoidism refers to a major form of interspecies interactions where parasitoids sterilize and/or kill their hosts typically before hosts reach reproductive age. However, relatively little is known about the evolutionary dynamics of parasitoidism. Here, we investigate the spatial patterns of genetic variation of Chinese cordyceps, including both the parasitoidal fungus Ophiocordyceps sinensis and its host insects. We sampled broadly from alpine regions on the Tibetan Plateau and obtained sequences on seven fungal and three insect DNA fragments from each of the 125 samples. Seven and five divergent lineages/cryptic species were identified within the fungus and host insects, respectively. Our analyses suggested that O . sinensis and host insects originated at similar geographic regions in southern Tibet/Yunnan, followed by range expansion to their current distributions. Cophylogenetic analyses revealed a complex evolutionary relationship between O. sinensis and its host insects. Significant congruence was found between host and parasite phylogenies and the time estimates of divergence were similar, raising the possibility of the occurrence of cospeciation events, but the incongruences suggested that host shifts were also prevalent. Interestingly, one fungal genotype was broadly distributed, consistent with recent gene flow. In contrast, the high‐frequency insect genotypes showed limited geographic distributions. The dominant genotypes from both the fungus and the insect hosts may represent ideal materials from which to develop artificial cultivation of this important Chinese traditional medicine. Our results demonstrate that both historical and contemporary events have played important roles in the phylogeography and evolution of the O. sinensis –ghost moth parasitoidism on the Tibetan Plateau.

Erratum to: Increase male genital diseases morbidity linked to informal electronic waste recycling in Guiyu, China - Xijin Xu; Yuling Zhang; Taofeek Akangbe Yekeen; Yan Li; Bingrong Zhuang; Xia Huo (Environmental Science and Pollution Research, 2014)

The Ph-3 gene from Solanum pimpinellifolium encodes CC-NBS-LRR protein conferring resistance to Phytophthora infestans - Chunzhi Zhang; Lei Liu; Xiaoxuan Wang; Jack Vossen; Guangcun Li; Tao Li; Zheng Zheng; Jianchang Gao; Yanmei Guo; Richard G. F. Visser; Junming Li; Yuling Bai; et al. (Theoretical and Applied Genetics, 2014)

Increase male genital diseases morbidity linked to informal electronic waste recycling in Guiyu, China - Xijin Xu; Yuling Zhang; Taofeek Akangbe Yekeen; Yan Li; Bingrong Zhuang; Xia Huo (Environmental Science and Pollution Research, 2014)

Novel antimicrobial metabolites produced by Sika deer-associated Actinomyces sp. JN411010 - Yujiao Tang; Yanmei Wang; Zhaohui Wang; Jing Zhang; Jianchun Qin; Quankai Wang; Lihua Yang; Lingzhi Xu; Yuling Ding; Yang Guo; Hongliang Li; Jingsi Li; et al. (Natural Product Research, 2013)

Fine mapping of the Ph-3 gene conferring resistance to late blight (Phytophthora infestans) in tomato - Chunzhi Zhang; Lei Liu; Zheng Zheng; Yuyan Sun; Longxi Zhou; Yuhong Yang; Feng Cheng; Zhonghua Zhang; Xiaowu Wang; Sanwen Huang; Bingyan Xie; Yongchen Du; et al. (Theoretical and Applied Genetics, 2013)

Synthesis, Crystal Structure and Photoluminescence of a Cyclometalated Iridium(III) Coumarin Complex - Tianzhi Yu; Chengcheng Zhang; Yuling Zhao; ShaoQiang Guo; Peng Liu; Wentao Li; Duowang Fan (Journal of Fluorescence, 2013)

Induction of apoptosis in HepG2 cells by polysaccharide MEP-II from the fermentation broth of Morchella esculenta - Meili Hu; Yan Chen; Cui Wang; Huali Cui; Peilu Duan; Tianlong Zhai; Yuling Yang; Shaofei Li (Biotechnology Letters, 2013)

The role of maize root size in phosphorus uptake and productivity of maize/faba bean and maize/wheat intercropping systems - YiKai Zhang; FanJun Chen; Long Li; YanHua Chen; BingRan Liu; YuLing Zhou; LiXing Yuan; FuSuo Zhang; GuoHua Mi (Science China Life Sciences, 2012)

High-level expression and characterization of a highly thermostable chitosanase from Aspergillus fumigatus in Pichia pastoris - Xiaomei Chen; Chao Zhai; Lixin Kang; Chunhua Li; Hong Yan; Yuling Zhou; Xiaolan Yu; Lixin Ma (Biotechnology Letters, 2012)

Identification and mapping of quantitative resistance to late blight (Phytophthora infestans) in Solanum habrochaites LA1777 - Junming Li; Lei Liu; Yuling Bai; Richard Finkers; Feng Wang; Yongchen Du; Yuhong Yang; Bingyan Xie; Richard G. F. Visser; Adriaan W. van Heusden (Euphytica, 2011)

Seedling salt tolerance in tomato - Junming Li; Lei Liu; Yuling Bai; Pujuan Zhang; Richard Finkers; Yongchen Du; Richard G. F. Visser; Adriaan W. van Heusden (Euphytica, 2011)

Pharmacokinetics of Anti-hepcidin Monoclonal Antibody Ab 12B9m and Hepcidin in Cynomolgus Monkeys - Jim J. Xiao; Wojciech Krzyzanski; Yow-Ming Wang; Hongyan Li; Mark J. Rose; Mark Ma; Yuling Wu; Beth Hinkle; Juan Jose Perez-Ruixo (The AAPS Journal, 2010)

Molecular cloning, sequence and expression analysis of ZmArf2, a maize ADP-ribosylation factor - Yanyang Liu; Junzhou Li; Yuling Li; Mengguan Wei; Qingxin Cui; Qilei Wang (Molecular Biology Reports, 2010)

QTL identification of grain protein concentration and its genetic correlation with starch concentration and grain weight using two populations in maize (Zea mays L.) - Yuling Li; Yanzhao Wang; Mengguan Wei; Xuehui Li; Jiafeng Fu (Journal of Genetics, 2009)

Effects of vegetation control on ecosystem water use efficiency within and among four grassland ecosystems in China - ZHONGMIN HU; GUIRUI YU; YULING FU; XIAOMIN SUN; YINGNIAN LI; PEILI SHI; YANFEN WANG; ZEMEI ZHENG (Global Change Biology, 2008)
Through 2–3‐year (2003–2005) continuous eddy covariance measurements of carbon dioxide and water vapor fluxes, we examined the seasonal, inter‐annual, and inter‐ecosystem variations in the ecosystem‐level water use efficiency (WUE, defined as the ratio of gross primary production, GPP, to evapotranspiration, ET) at four Chinese grassland ecosystems in the Qinghai‐Tibet Plateau and North China. Representing the most prevalent grassland types in China, the four ecosystems are an alpine swamp meadow ecosystem, an alpine shrub‐meadow ecosystem, an alpine meadow‐steppe ecosystem, and a temperate steppe ecosystem, which illustrate a water availability gradient and thus provide us an opportunity to quantify environmental and biological controls on ecosystem WUE at different spatiotemporal scales. Seasonally, WUE tracked closely with GPP at the four ecosystems, being low at the beginning and the end of the growing seasons and high during the active periods of plant growth. Such consistent correspondence between WUE and GPP suggested that photosynthetic processes were the dominant regulator of the seasonal variations in WUE. Further investigation indicated that the regulations were mainly due to the effect of leaf area index (LAI) on carbon assimilation and on the ratio of transpiration to ET ( T /ET). Besides, except for the swamp meadow, LAI also controlled the year‐to‐year and site‐to‐site variations in WUE in the same way, resulting in the years or sites with high productivity being accompanied by high WUE. The general good correlation between LAI and ecosystem WUE indicates that it may be possible to predict grassland ecosystem WUE simply with LAI. Our results also imply that climate change‐induced shifts in vegetation structure, and consequently LAI may have a significant impact on the relationship between ecosystem carbon and water cycles in grasslands.

Toxicological Protein Biomarker Analysis—An Investigative One-week Single Dose Intravenous Infusion Toxicity and Toxicokinetic Study in Cynomolgus Monkeys using an Antibody–cytotoxic Conjugate against Ovarian Cancer - Frank Y. Hsieh; Elizabeth Tengstrand; Lily Y. Li; Yuling N. Huang; Mark N. Milton; Lee Silverman; Carl Alden; Gerald Miwa; Frank Lee (Pharmaceutical Research, 2008)

High glucose induced human umbilical vein endothelial cell injury: involvement of protein tyrosine nitration - Yuling Zhao; Naihao Lu; Hailing Li; Yan Zhang; Zhonghong Gao; Yuefa Gong (Molecular and Cellular Biochemistry, 2008)

A mixture model approach to the mapping of QTL controlling endosperm traits with bulked samples - Xuefeng Wang; Zhiqiu Hu; Wei Wang; Yuling Li; Yuan-Ming Zhang; Chenwu Xu (Genetica, 2007)

Distinct reorganization of the genome transcription associates with organogenesis of somatic embryo, shoots, and roots in rice - Ning Su; Kun He; Yuling Jiao; Chen Chen; Junli Zhou; Lei Li; Sulan Bai; Xueyong Li; Xing Wang Deng (Plant Molecular Biology, 2007)

Tomato defense to the powdery mildew fungus: differences in expression of genes in susceptible, monogenic- and polygenic resistance responses are mainly in timing - Chengwei Li; Yuling Bai; Evert Jacobsen; Richard Visser; Pim Lindhout; Guusje Bonnema (Plant Molecular Biology, 2006)

Genetic and genotype × environment interaction effects analysis for erucic acid content in rapeseed (Brassica napus L.) - Chunhai Shi; Haizhen Zhang; Jianguo Wu; Changtao Li; Yuling Ren (Euphytica, 2003)

Contributory presentations/posters - N. Manoj; V. R. Srinivas; A. Surolia; M. Vijayan; K. Suguna; R. Ravishankar; K. Suguna; A. Surolia; M. Vijayan; R. Schwarzenbacher; K. Zeth; Diederichs; et al. (Journal of Biosciences, 1999)